West Antarctic subglacial geology distinguished by Pb isotopes and Rb–Sr ages in ice-rafted feldspars - Thomas Arney; Claus-Dieter Hillenbrand; Thomas M. Belgrano; J. Andy Milton; Christine S. Siddoway; Gavin L. Foster; Paul A. Wilson; Julia S. Wellner; Steve M. Bohaty (Earth and Planetary Science Letters, 2026)

Caldera faults can be sintered volcanic conduits without necessarily requiring catastrophic rapid slip events - Frankie L. Haywood; Fabian B. Wadsworth; Madeleine C.S. Humphreys; Dave McGarvie; Richard J. Brown; Alexander A. Iveson; Leon Bowen; Annabelle Foster (Earth and Planetary Science Letters, 2026)

Correction: The influence of mouth pressure on the cardiovascular response during inspiratory muscle loading at a constant transdiaphragmatic pressure - Megan L. Lance; Scott F. Thrall; Benjamin P. Thompson; Leah M. Mann; Jou-Chung Chang; Katherine M. Taylor; Nadia M. Navarro Solano; Madison J. Gorsline; Richard J. A. Wilson; Trevor A. Day; Paolo B. Dominelli; Glen E. Foster (European Journal of Applied Physiology, 2026)

Effect of separation distance between on-site sanitation systems and groundwater sources on faecal contamination: A systematic review and meta-analysis - Gita L. Putri; Elzavira Felaza; Cindy R. Priadi; Juliet Willetts; Tim Foster (Water Research, 2026)

Eight recommendations to enhance biodiversity outcomes of nature-based solutions at multiple scales - Charles B. van Rees; Collin VanBuren; Lori A. Han; Andrew Altieri; Matt Bilskie; James E. Byers; Jon Calabria; Matthew L. Chambers; Daniel J. Coleman; Katie Foster; Aliza Leit; Alec Nelson; et al. (Journal of Environmental Management, 2026)

Laboratory-grown crust in planktic foraminifera Neogloboquadrina pachyderma; insights into resolving inaccuracies in polar palaeotemperature estimates - Adele Westgård; Mohamed M. Ezat; Freya E. Sykes; Gavin L. Foster; Julie Meilland; Thomas B. Chalk; J. Andy Milton (Geochimica et Cosmochimica Acta, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The influence of mouth pressure on the cardiovascular response during inspiratory muscle loading at a constant transdiaphragmatic pressure - Megan L. Lance; Scott F. Thrall; Benjamin P. Thompson; Leah M. Mann; Jou-Chung Chang; Katherine M. Taylor; Nadia M. Navarro Solano; Madison J. Gorsline; Richard J. A. Wilson; Trevor A. Day; Paolo B. Dominelli; Glen E. Foster (European Journal of Applied Physiology, 2026)

Individual foraminiferal analysis: A promising tool for high-resolution temperature and pH reconstruction - Zifei Yang; Christopher D. Standish; Rachel M. Brown; Patrick A. Rafter; Malcolm B. Hart; Tali L. Babila; Gavin L. Foster (Chemical Geology, 2026)

Safety evaluation of a novel progesterone vaginal ring (PVR) for luteal phase support: SARA trial - Laurel A. Stadtmauer; Vicki L. Schnell; John K. Park; Cristin C. Slater; Eric D. Foster; Sarah A. Grover; Patrick W. Heiser (Drug Delivery and Translational Research, 2026)

Corrigendum to “Tracking the provenance of Greenland-sourced, Holocene aged, individual sand-sized ice-rafted debris using the Pb-isotope compositions of feldspars and 40Ar/39Ar ages of hornblendes” [Earth and Planetary Science Letters 433 (2016) 192–203] - Lee F. White; Ian Bailey; Gavin L. Foster; Georgina Allen; Simon P. Kelley; John T. Andrews; Kelly Hogan; Julian A. Dowdeswell; Craig D. Storey (Earth and Planetary Science Letters, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Spatiotemporal soil fertility responses to enhanced rock weathering along a hillslope catena within a temperate, agricultural watershed - Quinn C. Zacharias; Robert Rioux; Fengchao Sun; Wyatt Tatge; Evelin Pihlap; Emmanuel Nyavor; David A. Foster; Joshua L. Warren; Mark A. Bradford; Peter Raymond; Noah Planavsky; James Saiers (Nutrient Cycling in Agroecosystems, 2026)

Heat stress relief by tidally driven cold‐water bores on a coral reef atoll - Kelly Boden‐Hawes; Nicole L. Jones; Matthew D. Rayson; James P. Gilmour; Taryn Foster (Limnology and Oceanography, 2026)
Understanding how physical transport mechanisms influence coral reef temperature dynamics is crucial for effective management. Typically, sea surface temperature (SST) is used to estimate coral heat stress, yet subsurface physical processes can significantly influence reef temperature dynamics and are imperative to consider in predictive efforts. Using observations and a 3D numerical model, we conducted a volume‐based temperature budget analysis to investigate heat distribution at south Scott Reef, an atoll on the Australian North West Shelf. We identified how tidally driven processes influence the reef's heat budget by quantifying the volume flux of different temperature classes through each entrance. We found during the spring‐tide local, tidally driven cold‐water bores transported water ~ 2°C cooler than background through northwestern entrances of the lagoon semidiurnally leading to a net increase in cooler water. Coral surveys taken over the 2016 marine heatwave show sites exposed to the bores experienced a 0–10% reduction in coral cover compared to 10–60% in other regions. Using a dividing streamline model between January–May 1998–2022, we estimated water > 6°C cooler than recorded SST was delivered to the lagoon (40 m BSL) twice daily when tidally driven bores were active, that is, spring‐tide periods. Temperature differences between the surface and subsurface remained

Arsenic, cadmium, lead, mercury, and PFAS exposure during pregnancy or lactation and respective concentrations in human milk: Systematic review - Lauren E. O'Connor; Cassi N. Uffelman; Rachel C. Thoerig; Arin A. Balalian; Rupal Trivedi; Trish Bosse; Margaret J. Foster; Kyle M. Holland; Kathryn G. Dewey; Mandy M. Fisher; Aubrey L. Galusha; Carin A. Huset; et al. (Environmental Research, 2026)

Double cropping and tillage intensity in continuous wheat agroecosystems have variable impacts on soil hydrologic and physical properties - Perejitei E. Bekewe; Joseph A. Burke; Jamie L. Foster; Katie L. Lewis; Haly L. Neely; Clark B. Neely; Lauren E. Tomlin; Brandon Gerrish; Thomas W. Boutton (Soil and Tillage Research, 2026)

Production of sustainable aviation fuel-range hydrocarbons via thermal cracking of cumaru oil using red mud as a selective catalyst - Helvia Nancy Fuzer Lira; Roberto Freire da Silva; Sandro L. Barbosa; Foster A. Agblevor (Biomass and Bioenergy, 2026)

On-site sanitation systems and fecal contamination in shallow groundwater in urban Indonesia: assessing influence of distance and rainfall variables - Gita L. Putri; Akna M. Ilmi; Rahayu Handayani; Dadang Iskandar; Cindy R. Priadi; Juliet Willetts; Tim Foster (Water Research, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Global Patterns and Drivers of Seagrass Biomass, Net Primary Production and Meadow Structure - Nicole R. Foster; Enric Gomis; Diana I. Montemayor; Simone Strydom; Miguel Angel Mateo; Eduard Serrano; Aurora M. Ricart; Martin Dahl; Ines Mazarrasa; Paulina Cisternas; Harry Whiteley; Elliott J. Bates; et al. (Journal of Biogeography, 2025)
Aim We decipher global patterns in seagrass growth and structure to advance seagrass science, facilitate multidisciplinary research, and promote effective management strategies and policy development for seagrass habitats. Location: Global. Time period: 1975 to 2024. Major taxa studied: Seagrasses—marine angiosperms. Methods A global data set on seagrass total biomass, total net primary productivity (NPP), shoot density, and percent cover was compiled across 11 genera. We tested how these variables change across seagrass genera, life‐history strategy, and geographic location; and then modelled the environmental drivers (temperature, nutrients, light availability) of the patterns observed. Results The mean (±SE) total biomass of seagrasses globally was estimated at 340 ± 10 g DW m −2 and total NPP was estimated at 5.4 ± 0.4 g DW m −2 d −1 . Mean shoot density across all genera was 1,780 ± 67 shoots m −2 and percent cover was 42% ± 1%. Persistent genera showed the highest total biomass followed by opportunistic then colonising genera, whereas shoot density was higher for colonising than persistent, which had the highest percent cover. Latitudinal and bioregional patterns were identified for some genera and were mostly driven by genus‐specific traits, followed by localised environmental factors. Main Conclusions Trends in seagrass meadow ecology were largely influenced by seagrass genera and their life‐history strategy, with localised environmental factors, such as temperature and nutrients, also playing a role. Global estimates of seagrass biomass and NPP were 2‐times higher than previously reported. Seagrass life‐history strategies modulate the trade‐offs between NPP and biomass to thrive in specific habitats. This study provides the most updated global synthesis of patterns in seagrass growth and structure.

Parental Weaning Style Intent vs Reality: What Factors Affect If a Parent Intends and Completes Baby-led Weaning, Mixed Weaning, or Traditional Weaning - K. Whitley; D. Jacobvitz; S. Foster; L. Hernandez; M. Burgermaster; S. Dube; M. Abrego; A. Ramos-Gonzalez; M. Bradley; K. Ornelas; L. Sandoval-Mejia; I. Martinez; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

A Comparison of Acute Blood Glucose Response to 2% Lactaid Milk vs. 2% Regular Milk in Non-diabetic Adults - A. Kim; B. Vanyo; L. Foster-Nicholas; L. Ji; C. Kosch (Journal of the Academy of Nutrition and Dietetics, 2025)

Dietetics and Nursing Students Affirmatively Report the Likelihood of Recommending Predominantly Plant-based Diets for Non-communicable Disease Management - P. Dyett; L. Foster-Nicholas; C. Mitchell; V. Jones-Oyefeso; V. Sealey-Tobias; A. Adams-Robinson; P. Valley-Thom; D. Balfour (Journal of the Academy of Nutrition and Dietetics, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Timing of calcification and environmental variability determine pH proxy fidelity in coastal calcifying macroalgae - Ellen MacDonald; Maria Byrne; Dione J. Deaker; Gavin L. Foster; Sergio Torres Gabarda; John MacDonald; James W.B. Rae; Charlotte Slaymark; Nicholas A. Kamenos (Limnology and Oceanography, 2025)
Long‐lived calcifying marine biota are increasingly used as paleo‐archives for reconstructing ocean pH. They enable exploration of the rate and magnitude of ocean acidification in shallow‐water ecosystems serving as proxies for environmental pH reconstruction. However, shallow water systems often have highly variable carbonate chemistry, and the impact of this on the accuracy of pH reconstructions from long‐lived marine calcifiers is not known. In particular, a better understanding of the timing of calcification with respect to environmental pH cyclicity is needed. To test the fidelity of coastal environmental pH proxies, we assessed the synchronicity between calcification and in situ diel carbonate chemistry in a tropical (One Tree Island, Great Barrier Reef, Australia) and a temperate (Loch Sween, Scotland) location using calcifying macroalgae (rhodolith‐forming coralline algae) as a model system. Calcification occurred primarily during daylight hours, meaning a recording bias was introduced when compared to the full diel pH range (

Deep reinforcement learning-based optimization of an island energy-water microgrid system - Roozbeh Ghasemi; Gersi Doko; Marek Petrik; Martin Wosnik; Zhongming Lu; Diane L. Foster; Weiwei Mo (Resources, Conservation and Recycling, 2025)

Societal value of seagrass from historical to contemporary perspectives - Nicole R. Foster; Eugenia T. Apostolaki; Katelyn DiBenedetto; Carlos M. Duarte; David Gregory; Karina Inostroza; Dorte Krause-Jensen; Benjamin L. H. Jones; Eduard Serrano; Rym Zakhama-Sraieb; Oscar Serrano (Ambio, 2025)
Seagrasses have been entwined with human culture for millennia, constituting a natural resource that has supported humanity throughout this history. Understanding the societal value of seagrass fosters appreciation of these ecosystems, encouraging conservation and restoration actions to counteract historic and predicted losses. This study overviews the plethora of seagrass use in human history, ranging from spiritual and ceremonial roles, direct and indirect food resources, medicines and raw materials, dating back more than 180 000 years. While many past uses have been abandoned in modern societies, others have persisted or are being rediscovered, and new applications are emerging. As these uses of seagrasses depend on harvesting, we also underscore the need for sustainable practices to (re)generate positive interactions between seagrasses and society. Our review contributes to revalue seagrass societal ecosystem services, highlighting ancient and more recent human and seagrass relationships to incentivize conservation and restoration actions.

Satellite vs uncrewed aircraft systems (UAS): Combining high-resolution SkySat and UAS images for cotton yield estimation - Benjamin Ghansah; Jose L. Landivar Scott; Lei Zhao; Michael J. Starek; Jamie Foster; Juan Landivar; Mahendra Bhandari (Computers and Electronics in Agriculture, 2025)

Coverage matters: identifying and mitigating sampling frame issues in recreational fishing surveys - S. M. Taylor; A. de Groote; K. Hyder; J. H. Vølstad; B. W. Hartill; J. Foster; R. Andrews; K. L. Ryan (Reviews in Fish Biology and Fisheries, 2025)
Surveys play an integral part in monitoring and maintaining sustainable recreational fisheries. For any probabilistic survey, the selection of a sampling frame (e.g., list of individuals or fishers) is an important decision because it influences the ability to provide unbiased estimates of recreational catch and effort. Undercoverage occurs when units of the target population (i.e., the population of interest) are missing from the frame population. This error can undermine the reliability of research advice generated from survey estimates. In this review, we: (i) define six sampling frame configurations that are commonly applied in probabilistic recreational fishing surveys; (ii) synthesise how coverage errors associated with each configuration have been addressed for marine recreational fisheries globally; (iii) outline approaches to identify and correct for coverage errors; and (iv) recommend how to future-proof coverage issues. In our six case studies, multiple types of undercoverage were identified and addressed to varying extents, depending on the characteristics of each fishery and type of sampling frame used. Generalised list frames (particularly phone lists) are arguably the most prone to undercoverage error. To assist in future-proofing surveys, we recommend: (1) considering coverage error during survey planning; (2) designing pilot surveys or scheduling concurrent surveys to evaluate and/or correct for potential bias; (3) recognising that coverage error often changes through time; (4) using technological or multi-frame approaches to mitigate coverage error; (5) considering model-based survey tools to correct for undercoverage; and (6) documenting the sampling frame and potential sources of coverage error in publications. These recommendations extend to inland recreational fisheries, commercial fishing surveys and fisheries-independent surveys. Graphical abstract

Association mapping of haploid male fertility in sweet corn - Tyler L. Foster; Ursula K. Frei; Mercy Fakude; Matheus D. Krause; Sarah Pfeffer; Somak Dutta; William F. Tracy; Marcio F. R. Resende; Thomas Lübberstedt (Theoretical and Applied Genetics, 2025)

An interdisciplinary, co-teaching approach to a course in urban social-ecological systems - Vikki L. Rodgers; Stephen Deets; Sarah Foster; Paul Schmitz; Megan Way (Urban Ecosystems, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Major global ports alter light regimes for marine biofouling communities - Nina Schaefer; Melanie J. Bishop; Brett Herbert; Andrew S. Hoey; Mariana Mayer-Pinto; Craig D.H. Sherman; Cian Foster-Thorpe; Maria L. Vozzo; Katherine A. Dafforn (Journal of Environmental Management, 2025)

Physiological and morphological scaling enables gigantism in pelagic protists - Janet E. Burke; Leanne E. Elder; Amy E. Maas; Daniel E. Gaskell; Elizabeth G. Clark; Allison Y. Hsiang; Gavin L. Foster; Pincelli M. Hull (Limnology and Oceanography, 2025)
Planktonic foraminifera are pelagic protists frequently used to study paleoenvironmental change. Many planktonic foraminifera, like other taxa in Rhizaria, reach gigantic proportions relative to other pelagic protists (> 600 μ m), placing them in a size class dominated by metazoans. Here, we combine new and existing respiration rate measurements, micro‐CT scans, and test size measurements to investigate allometric scaling of metabolic rates, relative biomass density, and mixotrophy in contributing to the ability of planktonic foraminifera to reach large sizes. Respiration rate increases with foraminiferal biovolume with a slope of 0.51 ± 0.18. This allometric scaling slope is lower than those reported in other plankton. Further, the basal respiration rates for planktonic foraminifera exceed those of other organisms in their size class when probable biomass, rather than test volume, is considered. Using the allometric regression on a published database of modern planktonic foraminifera from the Atlantic Ocean, we estimate that gigantic individuals account for 15.3–26.1% of foraminiferal community respiration in temperate and tropical/subtropical latitudes, despite making up only 4.5–8.3% of individuals. We hypothesize that shallow scaling of test size with metabolism and of test size to actual biomass is the key factor allowing for gigantism in planktonic foraminifera. Having a large test and broadcasting rhizopodial networks increases the functional volume of the organism, allowing higher passive prey encounter rates to support the elevated metabolic rates in planktonic foraminifera. Mixotrophy may act as a mitigating factor for metabolic challenges at low latitudes, accounting for the presence of large populations of giant, predominately mixotrophic Rhizarians in these assemblages.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Effects of magnetically treated water on the survival of bacteria in biofilms - Aidan R. Foster; Erika R. Stark; Luisa A. Ikner; Ian L. Pepper (Biofouling, 2025)

Resistance- and endurance-trained young men display comparable carotid artery strain parameters that are superior to untrained men - Ian Hornby-Foster; Cory T. Richards; Aimee L. Drane; Freya M. Lodge; Michael Stembridge; Rachel N. Lord; Hannah Davey; Zaheer Yousef; Christopher J. A. Pugh (European Journal of Applied Physiology, 2025)
Purpose Central arterial stiffness, a predictor of cardiovascular risk, attenuates with endurance-exercise in ageing populations. However, in young individuals, this effect is inconsistent and emerging evidence suggests resistance-exercise may increase arterial stiffness. Two-dimensional (2D)-Strain imaging of the common carotid artery (CCA) is more sensitive at detecting endurance-training induced alterations in CCA stiffness than conventional methods, but has not been used to examine CCA stiffness in young resistance-trained individuals. Therefore, we compared CCA 2D-Strain parameters at rest, during acute exercise and recovery between resistance-trained, endurance-trained, and untrained young men. Methods Short-axis CCA ultrasound images were obtained from 12 endurance-trained [27yrs (95%CI; 24–29)], 14 resistance-trained [24yrs (23–26)] and 12 untrained [23yrs (22–24] men at rest, during isometric handgrip (IHG) exercise and recovery. 2D-Strain analysis quantified CCA peak circumferential strain (PCS) and systolic (S-SR) and diastolic (D-SR) strain rates. Conventional stiffness indices included aortic pulse-wave velocity, CCA β -stiffness ( β 1 ) and Petersons elastic modulus ( E p ). Results Resting conventional stiffness indices were not different between groups ( P > 0.05). Resting PCS and S-SR were comparable between resistance- [11.6% (10.6–12.5) and 1.46 s −1 (1.37–1.55), respectively] and endurance-trained [11.4% (10.7–12.2) and 1.5 s −1 (1.38–1.62)] men and superior to untrained men [9.5% (9.19–9.9); P < 0.004 and 1.24 s −1 (1.17 – 1.31); P < 0.018)]. Both trained groups displayed comparable reductions in PCS and S-SR during IHG, which returned to resting values during recovery ( P < 0.001), whereas these parameters remained unchanged in untrained men. D-SR decreased during IHG in all groups ( P < 0.001), but to a lesser extent in endurance-trained men ( P < 0.023), whereas β 1 and E p increased to a similar magnitude in all groups and returned to resting values during recovery ( P < 0.001). Conclusion Resistance- and endurance-trained men display comparable CCA 2D-Strain parameters that are superior to untrained men, which contends previous reports that resistance-training increases CCA stiffness.

2D geochemical imaging of biogenic marine carbonates using LA-TOF-ICP-MS at 1 and 2 μm pixel resolution - Christopher D. Standish; J. Andy Milton; Tessa M. Page; Rachel M. Brown; David Douglas; Bence Paul; Lukas Schlatt; Gavin L. Foster (Chemical Geology, 2024)

Historic ocean acidification of Loch Sween revealed by correlative geochemical imaging and high-resolution boron isotope analysis of Boreolithothamniom cf. soriferum - Ellen MacDonald; Gavin L. Foster; Christopher D. Standish; Jacob Trend; Tessa M. Page; Nicholas A. Kamenos (Earth and Planetary Science Letters, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Diverse and ecologically unique mesophotic coral ecosystems in the central Indian Ocean - C. Diaz; K. L. Howell; P. Hosegood; A. Bolton; N. L. Foster (Coral Reefs, 2024)
Research on Mesophotic Coral Ecosystems (MCEs; 30–150 m) has grown exponentially in the last few decades, highlighting their rich diversity and extensive distribution. However, they are still largely underexplored compared to shallow-water coral reefs and frequently remain under-protected and under-represented in marine spatial planning. One reason for the imbalance between the high ecological value of MCEs and the limited levels of protection may be that baseline data on MCEs are largely missing to date, yet are crucial to provide evidence-based information for management actions. Here, we present data on the alpha and beta diversity of the benthic communities within MCEs in the Chagos Archipelago, Indian Ocean. Using imagery collected from Remotely Operated Vehicle surveys, benthic invertebrate megafauna were surveyed along the entire depth gradient from shallow to lower mesophotic depths (15–160 m). The diversity of the benthic communities decreased with increasing depth, from shallow water to the lower mesophotic zone. Nevertheless, the deepest parts of MCEs in the Archipelago displayed higher species richness values than several other shallow subtropical regions. In addition, the benthic communities showed high dissimilarity along the depth gradient, indicating that the key driver of community composition change with depth is species turnover (species replacement), revealing the uniqueness of MCEs. This study presents novel findings on MCEs in the central Indian Ocean, demonstrating that they host a high and unique benthic diversity, and highlighting the need to protect these ecosystems to preserve the overall biodiversity of coral reefs.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Infrared photometry and spectrometry of satellites and debris at UKIRT - Eric C. Pearce; Harrison Krantz; Adam Block; Deatrick L. Foster (Journal of Space Safety Engineering, 2024)

Constitutive and numerical modelling for timber-metal connections under large deformations - L. M. Milindu B. Jayasekara; Robert M. Foster (Engineering Structures, 2024)

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

Influence of habitat features on the colonisation of native and non-indigenous species - Nina Schaefer; Melanie J. Bishop; Ana B. Bugnot; Cian Foster-Thorpe; Brett Herbert; Andrew S. Hoey; Mariana Mayer-Pinto; Shinichi Nakagawa; Craig D.H. Sherman; Maria L. Vozzo; Katherine A. Dafforn (Marine Environmental Research, 2024)

Geochemical proxies for deep-sea temperature and nutrient content in cold-water bamboo corals - Thomas J. Williams; Christopher D. Standish; Philippe Archambault; Jasmin A. Godbold; Martin Solan; Orestis L. Katsamenis; Philip J. Basford; Gavin L. Foster (Chemical Geology, 2024)

Synthesis and applications of manganese oxide - biochar composites: A systematic review across catalysis, capacitor and sorption applications - Flora M. Brocza; Stella J. Foster; Caroline L. Peacock; Jenny M. Jones (Biomass and Bioenergy, 2024)

Fine mapping of major QTL qshgd1 for spontaneous haploid genome doubling in maize (Zea mays L.) - Tyler L. Foster; Monika Kloiber-Maitz; Laurine Gilles; Ursula K. Frei; Sarah Pfeffer; Yu-Ru Chen; Somak Dutta; Arun S. Seetharam; Matthew B. Hufford; Thomas Lübberstedt (Theoretical and Applied Genetics, 2024)

Correction: Identifying opportunities for collective action around community nutrition programming through participatory systems science - Perla Chebli; Lan N. Đoàn; Rachel L. Thompson; Matthew Chin; Nasim Sabounchi; Victoria Foster; Terry T. K. Huang; Chau Trinh‑Shevrin; Simona C. Kwon; Stella S. Yi (Cancer Causes & Control, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Journals must expand access to peer review data - Olivia M. Smith; Kayla L. Davis; Robin Waterman; Riley B. Pizza; Caitlin Mack; Emily E. Conway; Kara C. Dobson; Brianna Foster; Ani E. Hristova; Julie C. Jarvey; Nan Nourn; Courtney L. Davis (Trends in Ecology & Evolution, 2024)

A combined compost, dolomite, and endophyte addition is more effective than single amendments for improving phytorestoration of metal contaminated mine tailings - Courtney A. Creamer; Mary-Cathrine Leewis; Martina Kracmarova-Farren; Jakub Papik; Sean Kacur; John Freeman; Ondrej Uhlik; Andrea L. Foster (Plant and Soil, 2024)
Background and aims Re-vegetation of mining-impacted landscapes reduces transport of toxic elements while improving soil fertility. This study evaluated whether the planting of a native perennial grass with a consortium of diazotrophic microbial endophytes and municipal waste compost—alone and in combination—enhanced plant growth while stabilizing metal(loids) in dolomite-amended tailings from a historically mined polymetallic mineral deposit. Methods We grew Bouteloua curtipendula seedlings in tailings with hazardous concentrations of As, Cd, Pb, Mn, and Zn. We evaluated how plant growth, organic matter accumulation, and major, minor, and trace element mobilization and phytostabilization responded to microbial endophyte and/or compost amendments after the 45-day growth experiment. Results Although most of the added endophytes were not uniquely identified, the best plant growth and fertility outcomes were achieved with a combination of amendments: dolomite to reduce acidity, compost to increase nitrogen, and a mixed consortium endophyte seed coating to synergistically increase organic carbon and grass biomass yields. Compost reduced shoot and root concentrations—but not yields—of contaminant metals. Endophytes increased foliar Cd, Co, Mn, and Pb yields but mobilized Pb and Zn from the tailings. Root stabilization of Cd, Co, Mn did not require amendments. Conclusion The most effective means of revegetating these acidic, polymetallic tailings with the native B. curtipendula is with a simultaneous dolomite, compost, and endophyte seed treatment. Due to potential phosphate solubilization and siderophore production by this consortium of endophytes, strategies to capture solubilized metal(loids) may be needed for sulfidic tailings with metal(loids) associated with mobile mineral phases.

Spatial pattern of seed arrival has a greater effect on plant diversity than does soil heterogeneity in a grassland ecosystem - Esben L. Kjaer; Gregory R. Houseman; Kobe N. Luu; Bryan L. Foster; Lauri Laanisto; Antonio J. Golubski (Plant and Soil, 2024)
Background and Aims Species diversity is expected to increase with environmental heterogeneity. For plant communities, this pattern has been confirmed by numerous observational studies. Yet, experimental studies yield inconsistent results potentially because of how experiments create soil heterogeneity or because seeds were sown homogeneously. Using a field experiment, we tested how soil heterogeneity, plant spatial aggregation via seed arrival, and grain size influence plant species richness in a restored grassland. Methods We manipulated soil heterogeneity and seed arrival in 0.2 × 0.2 or 0.4 × 04 m patches within each 4.0 × 4.6 m plot and allowed community assembly to occur for 4 growing seasons. Results Despite quantifiable soil differences, soil heterogeneity did not impact total or sown species richness, but did weakly influence non-sown richness. Richness differences were driven by non-sown plant species that likely exhibited higher establishment in aggregated plots due to decreased interspecific competition and conspecific facilitation. Conclusion Our results suggest that fine-scale soil heterogeneity weakly affects prairie plant diversity, but heterogeneous plant spatial structure can have a stronger effect on diversity. These results suggest that plant colonization may be the primary source of environmental heterogeneity and may explain inconsistent results from soil heterogeneity experiments.

Constraining uncertainty in boron isotope systematics using a Bayesian inversion engine reveals contrasting parameter sensitivities - Aled D. Evans; Gavin L. Foster; Damon A.H. Teagle (Chemical Geology, 2024)

Variable effects of substrate colour and microtexture on sessile marine taxa in Australian estuaries - Nina Schaefer; Melanie J. Bishop; Ana B. Bugnot; Brett Herbert; Andrew S. Hoey; Mariana Mayer-Pinto; Craig D. H. Sherman; Cian Foster-Thorpe; Maria L. Vozzo; Katherine A. Dafforn (Biofouling, 2024)

Effectiveness of monochloramine for inactivation of coronavirus in reclaimed water - Aidan R. Foster; Charles N. Haas; Charles P. Gerba; Ian L. Pepper (Science of The Total Environment, 2024)

The first report of Listeria monocytogenes detected in pinnipeds - Johanna L. Baily; Gavin K. Paterson; Geoffrey Foster; Nicholas J. Davison; Lineke Begeman; Ailsa J. Hall; Mark P. Dagleish (Journal of Comparative Pathology, 2024)

Organophosphate ester flame retardants and plasticizers in house dust and mental health outcomes among Canadian mothers: A nested prospective cohort study in CHILD - Stephanie A. Foster; Molly L. Kile; Perry Hystad; Miriam L. Diamond; Liisa M. Jantunen; Piush J. Mandhane; Theo J. Moraes; Garthika Navaranjan; James A. Scott; Elinor Simons; Padmaja Subbarao; Tim K. Takaro; et al. (Environmental Research, 2024)

DNA metabarcoding reveals diet composition of invasive rats and mice in Hawaiian forests - Sara M. E. Gabrielson; Rebecca L. Mau; Erika Dittmar; J. Patrick Kelley; Corey E. Tarwater; Donald R. Drake; Jinelle H. Sperry; Jeffrey T. Foster (Biological Invasions, 2024)

Identifying opportunities for collective action around community nutrition programming through participatory systems science - Perla Chebli; Lan N. Đoàn; Rachel L. Thompson; Matthew Chin; Nasim Sabounchi; Victoria Foster; Terry T. K. Huang; Chau Trinh-Shevrin; Simona C. Kwon; Stella S. Yi (Cancer Causes & Control, 2023)

Microbiomes associated with avian malaria survival differ between susceptible Hawaiian honeycreepers and sympatric malaria‐resistant introduced birds - Amanda K. Navine; Kristina L. Paxton; Eben H. Paxton; Patrick J. Hart; Jeffrey T. Foster; Nancy McInerney; Robert C. Fleischer; Elin Videvall (Molecular Ecology, 2023)
Of the estimated 55 Hawaiian honeycreepers (subfamily Carduelinae) only 17 species remain, nine of which the International Union for Conservation of Nature considers endangered. Among the most pressing threats to honeycreeper survival is avian malaria, caused by the introduced blood parasite Plasmodium relictum , which is increasing in distribution in Hawaiʻi as a result of climate change. Preventing further honeycreeper decline will require innovative conservation strategies that confront malaria from multiple angles. Research on mammals has revealed strong connections between gut microbiome composition and malaria susceptibility, illuminating a potential novel approach to malaria control through the manipulation of gut microbiota. One honeycreeper species, Hawaiʻi ʻamakihi ( Chlorodrepanis virens ), persists in areas of high malaria prevalence, indicating they have acquired some level of immunity. To investigate if avian host‐specific microbes may be associated with malaria survival, we characterized cloacal microbiomes and malaria infection for 174 ʻamakihi and 172 malaria‐resistant warbling white‐eyes ( Zosterops japonicus ) from Hawaiʻi Island using 16S rRNA gene metabarcoding and quantitative polymerase chain reaction. Neither microbial alpha nor beta diversity covaried with infection, but 149 microbes showed positive associations with malaria survivors. Among these were Escherichia and Lactobacillus spp . , which appear to mitigate malaria severity in mammalian hosts, revealing promising candidates for future probiotic research for augmenting malaria immunity in sensitive endangered species.

Extended one-generation reproductive toxicity study evaluating gardenia blue in Sprague Dawley rats - Melanie L. Foster; Debabrata Mahapatra; Robert R. Maronpot; Masayuki Nishino; Shuichi Chiba; Mihoko Koyanagi; Florence Burleson; Shim-mo Hayashi (Regulatory Toxicology and Pharmacology, 2023)

A Comparison of Infant Diet Quality Indices in Infants 7-12 Months Old - S. Foster; D. Jacobvitz; L. Hernandez; H. Jones; M. Abrego; E. Widen (Journal of the Academy of Nutrition and Dietetics, 2023)

Host infection and disease‐induced mortality modify species contributions to the environmental reservoir - Nichole A. Laggan; Katy L. Parise; J. Paul White; Heather M. Kaarakka; Jennifer A. Redell; John E. DePue; William H. Scullon; Joseph Kath; Jeffrey T. Foster; A. Marm Kilpatrick; Kate E. Langwig; Joseph R. Hoyt (Ecology, 2023)
Environmental pathogen reservoirs exist for many globally important diseases and can fuel epidemics, influence pathogen evolution, and increase the threat of host extinction. Species composition can be an important factor that shapes reservoir dynamics and ultimately determines the outcome of a disease outbreak. However, disease‐induced mortality can change species communities, indicating that species responsible for environmental reservoir maintenance may change over time. Here we examine the reservoir dynamics of Pseudogymnoascus destructans , the fungal pathogen that causes white‐nose syndrome in bats. We quantified changes in pathogen shedding, infection prevalence and intensity, host abundance, and the subsequent propagule pressure imposed by each species over time. We find that highly shedding species are important during pathogen invasion, but contribute less over time to environmental contamination as they also suffer the greatest declines. Less infected species remain more abundant, resulting in equivalent or higher propagule pressure. More broadly, we demonstrate that high infection intensity and subsequent mortality during disease progression can reduce the contributions of high‐shedding species to long‐term pathogen maintenance.

Adaptation and mitigation capacity of wildland forests in the northeastern United States - Edward K. Faison; Danelle Laflower; Luca L. Morreale; David R. Foster; Brian Hall; Emily Johnson; Jonathan R. Thompson (Forest Ecology and Management, 2023)

The history of ice-sheet retreat on North America during Termination 5: Implications for the origin of the sea-level highstand during interglacial stage 11 - Rebecca L. Parker; Gavin L. Foster; Marcus Gutjahr; Paul A. Wilson; Stephen P. Obrochta; Nathalie Fagel; Matthew J. Cooper; Agnes Michalik; James A. Milton; Ian Bailey (Earth and Planetary Science Letters, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

The distribution of metal and petroleum-derived contaminants within sediments around oil and gas infrastructure in the Gippsland Basin, Australia - Sharon E. Hook; Scott Foster; Franziska Althaus; Douglas Bearham; Brad M. Angel; Andrew T. Revill; Stuart L. Simpson; Joanna Strzelecki; Tom Cresswell; Keith R. Hayes (Marine Pollution Bulletin, 2023)

A scenario-specific nexus modelling toolkit to identify trade-offs in the promotion of sustainable irrigated agriculture in Ecuador, a Belt and Road country - L. Naranjo; M.E. Correa-Cano; D. Rey; R. Chengot; F. España; M. Sactic; J.W. Knox; X. Yan; O. Viteri-Salazar; W. Foster; O. Melo (Journal of Cleaner Production, 2023)

Correction: Impact of nitrogen (N) and phosphorus (P) enrichment and skewed N:P stoichiometry on the skeletal formation and microstructure of symbiotic reef corals - M. C. Buckingham; C. D’Angelo; T. B. Chalk; G. L. Foster; K. G. Johnson; Z. Connelly; C. Olla; M. Saeed; J. Wiedenmann (Coral Reefs, 2023)

Potassium and magnesium uptake and fertiliser use efficiency by oil palm at contrasting sites in Sumatra, Indonesia - Noto E. Prabowo; Hugh L. Foster; Paul N. Nelson (Nutrient Cycling in Agroecosystems, 2023)
The accuracy of fertiliser recommendations can be improved by knowledge of use efficiency of applied nutrients. The aim of this work was to determine the efficiency with which mature oil palm ( Elaeis guineensis Jacq.) recovers and uses fertiliser K and Mg under different environmental conditions in Sumatra, Indonesia. The work was carried out in seven factorial fertiliser trials (NPKMg) at sites with contrasting soils, slope and rainfall (1500–3500 mm annual average). We recorded the palms’ fresh fruit bunch yield (weekly), vegetative growth and nutrient content (annually), and soil properties (once during the study) over three years. Nutrient content of the above-ground palm components was calculated by multiplying concentration by biomass. Palm responses to K and Mg application were analysed at non-limiting values of the other nutrients. Fresh fruit bunch yield was significantly increased by application of K in five of the seven sites (by 4.8–11.9 t ha −1 ) and by Mg in two of the seven sites (by 7.2–12.3 t ha −1 ). Application of these fertilisers also significantly increased growth and nutrient content in most situations. Nutrient use efficiency declined with increasing yield and nutrient uptake. In the five sites with most positive yield responses to K, agronomic efficiency of K and Mg differed between sites due to differences in recovery efficiency. Recovery efficiency was correlated positively to soil K, Mg and silt content and rainfall, and negatively to slope and soil moisture deficit. In contrast, physiological efficiency of K and Mg use was similar across sites, despite differences in palm age and planting density. It thus appeared that physiological efficiency was determined by genotype and that variation in agronomic efficiency was mostly a result of differences in recovery efficiency.

Hydrodynamics and Sediment-Transport Pathways along a Mixed-Energy Spit-Inlet System: A Modeling Study at Chincoteague Inlet (Virginia, USA) - Ioannis Y. Georgiou; Francesca Messina; Md Mohiuddin Sakib; Shan Zou; Madeline Foster-Martinez; Martijn Bregman; Christopher J. Hein; Michael S. Fenster; Justin L. Shawler; Kaitlyn McPherran; Arthur C. Trembanis (Journal of Marine Science and Engineering, 2023)
Tidal-inlet systems are dynamic features that respond to short-term (e.g., storms) and longer-term processes (e.g., sea-level rise, changes in tidal prism). The Chincoteague Inlet system, located along the northern Eastern Shore of Virginia (USA), is a dynamic coastal complex that experiences rapid change associated with sediment redistribution and a shifting inlet throat due to the southern elongation of adjacent Assateague Island. In this study, a numerical model based on Delft3D with coupled flow–waves, multiclass sediment transport, and morphologic feedback was developed to quantify the hydrodynamic and geomorphic controls within this rapidly evolving inlet–spit system and to develop a more comprehensive understanding of regional to local controls on sediment-transport pathways. Model results show that most of the sand transport along southern Assateague Island is sequestered nearshore and proximally in deeper sinks within Fishing Point, and, of that, only finer sand sizes are transported around the spit, confirming previous analysis and hypothesis. The model also showed that sand transport toward the south increases along Wallops Island and quantified spatially explicit transport trends for selected sediment classes, revealing that coarser sediment bypassing is a punctuated process that is proportional to storms.

Nowhere to fly: Avian malaria is ubiquitous from ocean to summit on a Hawaiian island - John H. Neddermeyer; Katy L. Parise; Erika Dittmar; A. Marm Kilpatrick; Jeffrey T. Foster (Biological Conservation, 2023)

Variant-specific SARS-CoV-2 shedding rates in wastewater - Sarah M. Prasek; Ian L. Pepper; Gabriel K. Innes; Stephanie Slinski; Walter Q. Betancourt; Aidan R. Foster; Hayley D. Yaglom; W. Tanner Porter; David M. Engelthaler; Bradley W. Schmitz (Science of The Total Environment, 2023)

Boron isotopes in blue diamond record seawater-derived fluids in the lower mantle - Margo E. Regier; Karen V. Smit; Thomas B. Chalk; Thomas Stachel; Richard A. Stern; Evan M. Smith; Gavin L. Foster; Yannick Bussweiler; Chris DeBuhr; Antony D. Burnham; Jeff W. Harris; D. Graham Pearson (Earth and Planetary Science Letters, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Impact of nitrogen (N) and phosphorus (P) enrichment and skewed N:P stoichiometry on the skeletal formation and microstructure of symbiotic reef corals - M. C. Buckingham; C. D’Angelo; T. B. Chalk; G. L. Foster; K. G. Johnson; Z. Connelly; C. Olla; M. Saeed; J. Wiedenmann (Coral Reefs, 2022)
Reported divergent responses of coral growth and skeletal microstructure to the nutrient environment complicate knowledge-based management of water quality in coral reefs. By re-evaluating published results considering the taxonomy of the studied corals and the N:P stoichiometry of their nutrient environment, we could resolve some of the major apparent contradictions. Our analysis suggests that Acroporids behave differently to several other common genera and show distinct responses to specific nutrient treatments. We hypothesised that both the concentrations of dissolved inorganic N and P in the water and their stoichiometry shape skeletal growth and microstructure. We tested this hypothesis by exposing Acropora polystoma fragments to four nutrient treatments for > 10 weeks: high nitrate/high phosphate (HNHP), high nitrate/low phosphate (HNLP), low nitrate/high phosphate (LNHP) and low nitrate/low phosphate (LNLP). HNHP corals retained high zooxanthellae densities and their linear extension and calcification rates were up to ten times higher than in the other treatments. HNLP and LNLP corals bleached through loss of symbionts. The photochemical efficiency (Fv/Fm) of residual symbionts in HNLP corals was significantly reduced, indicating P-starvation. Micro-computed tomography (µCT) of the skeletal microstructure revealed that reduced linear extension in nutrient limited or nutrient starved conditions (HNLP, LNHP, LNLP) was associated with significant thickening of skeletal elements and reduced porosity. These changes can be explained by the strongly reduced linear extension rate in combination with a smaller reduction in the calcification rate. Studies using increased skeletal density as a proxy for past thermal bleaching events should consider that such an increase in density may also be associated with temperature-independent response to the nutrient environment. Furthermore, the taxonomy of corals and seawater N:P stoichiometry should be considered when analysing and managing the impacts of nutrient pollution.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Nitrogen Fertilizer, Arbuscular Mycorrhizal Fungi, and Soil Nematodes Affect Lignin Quality and Quantity in Switchgrass (Panicum virgatum L.) - Binod Basyal; Cliff Foster; Katherine L. Gross; Sarah M. Emery (BioEnergy Research, 2022)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Microbial mediators of plant community response to long‐term N and P fertilization: Evidence of a role of plant responsiveness to mycorrhizal fungi - Guangzhou Wang; Liz Koziol; Bryan L. Foster; James D. Bever (Global Change Biology, 2022)
Climate changes and anthropogenic nutrient enrichment widely threaten plant diversity and ecosystem functions. Understanding the mechanisms governing plant species turnover across nutrient gradients is crucial to developing successful management and restoration strategies. We tested whether and how soil microbes, particularly arbuscular mycorrhizal fungi (AMF), could mediate plant community response to a 15 years long‐term N (0, 4, 8, and 16 g N m −2 year −1 ) and P (0 and 8 g N m −2 year −1 ) enrichment in a grassland system. We found N and P enrichment resulted in plant community diversity decrease and composition change, in which perennial C 4 graminoids were dramatically reduced while annuals and perennial forbs increased. Metabarcoding analysis of soil fungal community showed that N and P changed fungal diversity and composition, of which only a cluster of AMF identified by the co‐occurrence networks analysis was highly sensitive to P treatments and was negatively correlated with shifts in percentage cover of perennial C 4 graminoids. Moreover, by estimating the mycorrhizal responsiveness (MR) of 41 plant species in the field experiment from 264 independent tests, we found that the community weighted mean MR of the plant community was substantially reduced with nutrient enrichment and was positively correlated with C 4 graminoids percentage cover. Both analyses of covariance and structural equation modeling indicated that the shift in MR rather than AMF composition change was the primary predictor of the decline in perennial C 4 graminoids, suggesting that the energy cost invested by C 4 plants on those sensitive AMF might drive the inferior competitive abilities compared with other groups. Our results suggest that shifts in the competitive ability of mycorrhizal responsive plants can drive plant community change to anthropogenic eutrophication, suggesting a functional benefit of mycorrhizal mutualism in ecological restoration following climatic or anthropogenic degradation of soil communities.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

RGS14 modulates locomotor behavior and ERK signaling induced by environmental novelty and cocaine within discrete limbic structures - Stephanie L. Foster; Daniel J. Lustberg; Nicholas H. Harbin; Sara N. Bramlett; John R. Hepler; David Weinshenker (Psychopharmacology, 2021)

Determinants of community compositional change are equally affected by global change - Meghan L. Avolio; Kimberly J. Komatsu; Scott L. Collins; Emily Grman; Sally E. Koerner; Andrew T. Tredennick; Kevin R. Wilcox; Sara Baer; Elizabeth H. Boughton; Andrea J. Britton; Bryan Foster; Laura Gough; et al. (Ecology Letters, 2021)
Global change is impacting plant community composition, but the mechanisms underlying these changes are unclear. Using a dataset of 58 global change experiments, we tested the five fundamental mechanisms of community change: changes in evenness and richness, reordering, species gains and losses. We found 71% of communities were impacted by global change treatments, and 88% of communities that were exposed to two or more global change drivers were impacted. Further, all mechanisms of change were equally likely to be affected by global change treatments—species losses and changes in richness were just as common as species gains and reordering. We also found no evidence of a progression of community changes, for example, reordering and changes in evenness did not precede species gains and losses. We demonstrate that all processes underlying plant community composition changes are equally affected by treatments and often occur simultaneously, necessitating a wholistic approach to quantifying community changes.

Sediment source fingerprinting: benchmarking recent outputs, remaining challenges and emerging themes - Adrian L. Collins; Martin Blackwell; Pascal Boeckx; Charlotte-Anne Chivers; Monica Emelko; Olivier Evrard; Ian Foster; Allen Gellis; Hamid Gholami; Steve Granger; Paul Harris; Arthur J. Horowitz; et al. (Journal of Soils and Sediments, 2020)
Purpose This review of sediment source fingerprinting assesses the current state-of-the-art, remaining challenges and emerging themes. It combines inputs from international scientists either with track records in the approach or with expertise relevant to progressing the science. Methods Web of Science and Google Scholar were used to review published papers spanning the period 2013–2019, inclusive, to confirm publication trends in quantities of papers by study area country and the types of tracers used. The most recent (2018–2019, inclusive) papers were also benchmarked using a methodological decision-tree published in 2017. Scope Areas requiring further research and international consensus on methodological detail are reviewed, and these comprise spatial variability in tracers and corresponding sampling implications for end-members, temporal variability in tracers and sampling implications for end-members and target sediment, tracer conservation and knowledge-based pre-selection, the physico-chemical basis for source discrimination and dissemination of fingerprinting results to stakeholders. Emerging themes are also discussed: novel tracers, concentration-dependence for biomarkers, combining sediment fingerprinting and age-dating, applications to sediment-bound pollutants, incorporation of supportive spatial information to augment discrimination and modelling, aeolian sediment source fingerprinting, integration with process-based models and development of open-access software tools for data processing. Conclusions The popularity of sediment source fingerprinting continues on an upward trend globally, but with this growth comes issues surrounding lack of standardisation and procedural diversity. Nonetheless, the last 2 years have also evidenced growing uptake of critical requirements for robust applications and this review is intended to signpost investigators, both old and new, towards these benchmarks and remaining research challenges for, and emerging options for different applications of, the fingerprinting approach.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Genetic analyses of native Fusarium head blight resistance in two spring wheat populations identifies QTL near the B1, Ppd-D1, Rht-1, Vrn-1, Fhb1, Fhb2, and Fhb5 loci - Dinushika Thambugala; Anita L. Brûlé-Babel; Barbara A. Blackwell; George Fedak; Adam J. Foster; Dan MacEachern; Jeannie Gilbert; Maria Antonia Henriquez; Richard A. Martin; Brent D. McCallum; Dean Spaner; Muhammad Iqbal; et al. (Theoretical and Applied Genetics, 2020)

Potential physical effects of suspended fine sediment on lotic macroinvertebrates - Morwenna McKenzie; Kate L. Mathers; Paul J. Wood; Judy England; Ian Foster; Damian Lawler; Martin Wilkes (Hydrobiologia, 2020)

Age and Sex Influence the Hippocampal Response and Recovery Following Sepsis - Jolie Barter; Ashok Kumar; Julie A. Stortz; McKenzie Hollen; Dina Nacionales; Philip A. Efron; Lyle L. Moldawer; Thomas C. Foster (Molecular Neurobiology, 2019)

The descending motor tracts are different in dancers and musicians - Chiara Giacosa; Falisha J. Karpati; Nicholas E. V. Foster; Krista L. Hyde; Virginia B. Penhune (Brain Structure and Function, 2019)

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

Physical mechanisms influencing localized patterns of temperature variability and coral bleaching within a system of reef atolls - Rebecca H. Green; Ryan J. Lowe; Mark L. Buckley; Taryn Foster; James P. Gilmour (Coral Reefs, 2019)

Integrated in vitro models for hepatic safety and metabolism: evaluation of a human Liver-Chip and liver spheroid - Alison J. Foster; Bhavik Chouhan; Sophie L. Regan; Helen Rollison; Sara Amberntsson; Linda C. Andersson; Abhishek Srivastava; Malin Darnell; Jonathan Cairns; Stanley E. Lazic; Kyung-Jin Jang; Debora B. Petropolis; et al. (Archives of Toxicology, 2019)

The effects of trehalose glycolipid presentation on cytokine production by GM-CSF macrophages - Bridget L. Stocker; Kristel Kodar; Kanu Wahi; Amy J. Foster; Jacquie L. Harper; Daiki Mori; Sho Yamasaki; Mattie S. M. Timmer (Glycoconjugate Journal, 2019)

Analysis of novel domain-specific mutations in the zebrafish ndr2/cyclops gene generated using CRISPR-Cas9 RNPs - Ashley N. Turner; Reagan S. Andersen; Ivy E. Bookout; Lauren N. Brashear; James C. Davis; David M. Gahan; John P. Gotham; Baraa A. Hijaz; Ashish S. Kaushik; Jordan B. Mcgill; Victoria L. Miller; Zachariah P. Moseley; et al. (Journal of Genetics, 2018)

Ambient changes exceed treatment effects on plant species abundance in global change experiments - J. Adam Langley; Samantha K. Chapman; Kimberly J. La Pierre; Meghan Avolio; William D. Bowman; David S. Johnson; Forest Isbell; Kevin R. Wilcox; Bryan L. Foster; Mark J. Hovenden; Alan K. Knapp; Sally E. Koerner; et al. (Global Change Biology, 2018)
The responses of species to environmental changes will determine future community composition and ecosystem function. Many syntheses of global change experiments examine the magnitude of treatment effect sizes, but we lack an understanding of how plant responses to treatments compare to ongoing changes in the unmanipulated (ambient or background) system. We used a database of long‐term global change studies manipulating CO 2 , nutrients, water, and temperature to answer three questions: (a) How do changes in plant species abundance in ambient plots relate to those in treated plots? (b) How does the magnitude of ambient change in species‐level abundance over time relate to responsiveness to global change treatments? (c) Does the direction of species‐level responses to global change treatments differ from the direction of ambient change? We estimated temporal trends in plant abundance for 791 plant species in ambient and treated plots across 16 long‐term global change experiments yielding 2,116 experiment–species–treatment combinations. Surprisingly, for most species (57%) the magnitude of ambient change was greater than the magnitude of treatment effects. However, the direction of ambient change, whether a species was increasing or decreasing in abundance under ambient conditions, had no bearing on the direction of treatment effects. Although ambient communities are inherently dynamic, there is now widespread evidence that anthropogenic drivers are directionally altering plant communities in many ecosystems. Thus, global change treatment effects must be interpreted in the context of plant species trajectories that are likely driven by ongoing environmental changes.

Changes in the trade of bycatch species corresponding to CITES regulations: the case of dried seahorse trade in Thailand - T.-C. Kuo; P. Laksanawimol; L. Aylesworth; S. J. Foster; A. C. J. Vincent (Biodiversity and Conservation, 2018)

Reproducible multi-parameter acoustic detection of seasonal drift macroalgae in the Indian River Lagoon, Florida - G. Foster; B. M. Riegl; L. J. Morris; K. A. Foster (Journal of Coastal Conservation, 2018)

Transcriptome response of the foundation plant Spartina alterniflora to the Deepwater Horizon oil spill - Mariano Alvarez; Julie Ferreira de Carvalho; Armel Salmon; Malika L. Ainouche; Armand Cavé‐Radet; Abdelhak El Amrani; Tammy E. Foster; Sydney Moyer; Christina L. Richards (Molecular Ecology, 2018)
Despite the severe impacts of the Deepwater Horizon oil spill, the foundation plant species Spartina alterniflora proved resilient to heavy oiling, providing an opportunity to identify mechanisms of response to the anthropogenic stress of crude oil exposure. We assessed plants from oil‐affected and unaffected populations using a custom DNA microarray to identify genomewide transcription patterns and gene expression networks that respond to crude oil exposure. In addition, we used T‐DNA insertion lines of the model grass Brachypodium distachyon to assess the contribution of four novel candidate genes to crude oil response. Responses in S. alterniflora to hydrocarbon exposure across the transcriptome as well as xenobiotic specific response pathways had little overlap with those previously identified in the model plant Arabidopsis thaliana . Among T‐DNA insertion lines of B. distachyon , we found additional support for two candidate genes, one (ATTPS21) involved in volatile production, and the other (SUVH5) involved in epigenetic regulation of gene expression, that may be important in the response to crude oil. The architecture of crude oil response in S. alterniflora is unique from that of the model species A. thaliana, suggesting that xenobiotic response may be highly variable across plant species. In addition, further investigations of regulatory networks may benefit from more information about epigenetic response pathways.

An analysis of potential controls on long-term 137Cs accumulation in the sediments of UK lakes - Simon Pulley; Ian D. L. Foster; Adrian L. Collins; Yusheng Zhang; Jennine Evans (Journal of Paleolimnology, 2018)

The duality of ocean acidification as a resource and a stressor - Sean D. Connell; Zoë A. Doubleday; Nicole R. Foster; Sarah B. Hamlyn; Christopher D. G. Harley; Brian Helmuth; Brendan P. Kelaher; Ivan Nagelkerken; Kirsten L. Rodgers; Gianluca Sarà; Bayden D. Russell (Ecology, 2018)
Ecologically dominant species often define ecosystem states, but as human disturbances intensify, their subordinate counterparts increasingly displace them. We consider the duality of disturbance by examining how environmental drivers can simultaneously act as a stressor to dominant species and as a resource to subordinates. Using a model ecosystem, we demonstrate that CO 2 ‐driven interactions between species can account for such reversals in dominance; i.e., the displacement of dominants (kelp forests) by subordinates (turf algae). We established that CO 2 enrichment had a direct positive effect on productivity of turfs, but a negligible effect on kelp. CO 2 enrichment further suppressed the abundance and feeding rate of the primary grazer of turfs (sea urchins), but had an opposite effect on the minor grazer (gastropods). Thus, boosted production of subordinate producers, exacerbated by a net reduction in its consumption by primary grazers, accounts for community change (i.e., turf displacing kelp). Ecosystem collapse, therefore, is more likely when resource enrichment alters competitive dominance of producers, and consumers fail to compensate. By recognizing such duality in the responses of interacting species to disturbance, which may stabilize or exacerbate change, we can begin to understand how intensifying human disturbances determine whether or not ecosystems undergo phase shifts.

Spatial and temporal interactions of free-ranging pacas (Cuniculus paca) - Bart J. Harmsen; Rebecca L. Wooldridge; Said M. Gutierrez; C. Patrick Doncaster; Rebecca J. Foster (Mammal Research, 2018)

Hydrogeological typologies of the Indo-Gangetic basin alluvial aquifer, South Asia - H. C. Bonsor; A. M. MacDonald; K. M. Ahmed; W. G. Burgess; M. Basharat; R. C. Calow; A. Dixit; S. S. D. Foster; K. Gopal; D. J. Lapworth; M. Moench; A. Mukherjee; et al. (Hydrogeology Journal, 2017)

Urban development in the southern Great Plains: effects of atmospheric NOx on the long-lived post oak tree (Quercus stellata) - Michelle L Green; Kalee Foster; Laura Gough (Urban Ecosystems, 2017)

Spatial and temporal variation of diverse inter‐tidal algal assemblages in Southwest O‘ahu - Traci Erin Cox; Heather L. Spalding; Michael S. Foster (Marine Ecology, 2017)
Spatial and temporal variation in tropical inter‐tidal communities is poorly known, making predictions about the effects of climate change and other anthropogenic disturbances difficult. Along Southwest O‘ahu, Hawai'i, local residents are concerned about the environmental effects of coastal development and the perceived loss of targeted algal species, which are collected for human consumption. To describe the coastal benthic community and better understand the processes that form and maintain it, the abundance and composition of macroalgae were sampled in the region's inter‐tidal zone from 2006 to 2015. Sixty‐six macroalgal species and two broad algal assemblages were identified that corresponded to substrate topography and sand influence at a similar tidal elevation. Along flat carbonate benches with a sand beach, Phaeophyceae and Rhodophytes occurred in almost equal proportions, while shores with slightly more topographic relief and angular substrate were dominated by Rhodophytes. Foliose or turf algal forms were most common. Surveys captured the local invasion of an alga, Avrainvillea sp. and significant declines in abundant macroalgae in 2015 after a period of unseasonably warm, calm water. Temporal changes in algal assemblages were related to maximum water temperature and wave height but not precipitation. Thus, algal assemblages appear to be structured by local beach morphology as they interact with sand and wave activity and episodically by unusual weather events. However, manipulation and continuous monitoring of the algal assemblages coupled to sensing of the localized environment is necessary to confirm factors related to assembly maintenance and recent species shifts.

Pathogen dynamics during invasion and establishment of white‐nose syndrome explain mechanisms of host persistence - Winifred F. Frick; Tina L. Cheng; Kate E. Langwig; Joseph R. Hoyt; Amanda F. Janicki; Katy L. Parise; Jeffrey T. Foster; A. Marm Kilpatrick (Ecology, 2017)
Disease dynamics during pathogen invasion and establishment determine the impacts of disease on host populations and determine the mechanisms of host persistence. Temporal progression of prevalence and infection intensity illustrate whether tolerance, resistance, reduced transmission, or demographic compensation allow initially declining populations to persist. We measured infection dynamics of the fungal pathogen Pseudogymnoascus destructans that causes white‐nose syndrome in bats by estimating pathogen prevalence and load in seven bat species at 167 hibernacula over a decade as the pathogen invaded, became established, and some host populations stabilized. Fungal loads increased rapidly and prevalence rose to nearly 100% at most sites within 2 yr of invasion in six of seven species. Prevalence and loads did not decline over time despite huge reductions in colony sizes, likely due to an extensive environmental reservoir. However, there was substantial variation in fungal load among sites with persisting colonies, suggesting that both tolerance and resistance developed at different sites in the same species. In contrast, one species disappeared from hibernacula within 3 yr of pathogen invasion. Variable host responses to pathogen invasion require different management strategies to prevent disease‐induced extinction and to facilitate evolution of tolerance or resistance in persisting populations.

Observations of pockmark flow structure in Belfast Bay, Maine, Part 3: implications for sediment transport - Christina L. Fandel; Thomas C. Lippmann; Diane L. Foster; Laura L. Brothers (Geo-Marine Letters, 2017)

Observations of pockmark flow structure in Belfast Bay, Maine, Part 2: evidence for cavity flow - Christina L. Fandel; Thomas C. Lippmann; Diane L. Foster; Laura L. Brothers (Geo-Marine Letters, 2017)

Freeze–thaw cycles have minimal effect on the mineralisation of low molecular weight, dissolved organic carbon in Arctic soils - A. Foster; D. L. Jones; E. J. Cooper; P. Roberts (Polar Biology, 2016)

Lessons on Climate Sensitivity From Past Climate Changes - Anna S. von der Heydt; Henk A. Dijkstra; Roderik S. W. van de Wal; Rodrigo Caballero; Michel Crucifix; Gavin L. Foster; Matthew Huber; Peter Köhler; Eelco Rohling; Paul J. Valdes; Peter Ashwin; Sebastian Bathiany; et al. (Current Climate Change Reports, 2016)

Soybean Aphid Response to their Alarm Pheromone E-ß-Farnesene (EBF) - Jaclyn L. Eichele; Jamin Dreyer; Ray Heinz; Stephen P. Foster; Deirdre A. Prischmann-Voldseth; Jason P. Harmon (Journal of Insect Behavior, 2016)

The effect of high dose oral manganese exposure on copper, iron and zinc levels in rats - Courtney J. Mercadante; Carolina Herrera; Michael A. Pettiglio; Melanie L. Foster; Laura C. Johnson; David C. Dorman; Thomas B. Bartnikas (BioMetals, 2016)

Sensorimotor integration is enhanced in dancers and musicians - Falisha J. Karpati; Chiara Giacosa; Nicholas E. V. Foster; Virginia B. Penhune; Krista L. Hyde (Experimental Brain Research, 2016)

S almonella infection in grey seals ( H alichoerus grypus ), a marine mammal sentinel species: pathogenicity and molecular typing of S almonella strains compared with human and livestock isolates - Johanna L. Baily; Geoffrey Foster; Derek Brown; Nicholas J. Davison; John E. Coia; Eleanor Watson; Romain Pizzi; Kim Willoughby; Ailsa J. Hall; Mark P. Dagleish (Environmental Microbiology, 2016)
Summary Microbial pollution of the marine environment through land–sea transfer of human and livestock pathogens is of concern. S almonella was isolated from rectal swabs of free‐ranging and stranded grey seal pups (21.1%; 37/175) and compared with strains from the same serovars isolated from human clinical cases, livestock, wild mammals and birds in Scotland, UK to characterize possible transmission routes using pulsed‐field gel electrophoresis and multi‐locus variable number of tandem repeat analyses. A higher prevalence of S almonella was found in pups exposed to seawater, suggesting that this may represent a source of this pathogen. S almonella Bovismorbificans was the most common isolate (18.3% pups; 32/175) and was indistinguishable from isolates found in Scottish cattle. S almonella T yphimurium was infrequent (2.3% pups; 4/175), mostly similar to isolates found in garden birds and, in one case, identical to a highly multidrug resistant strain isolated from a human child. S almonella H aifa was rare (1.1% pups; 2/175), but isolates were indistinguishable from that of a human clinical isolate. These results suggest that S . Bovismorbificans may circulate between grey seal and cattle populations and that both S . Typhimurium and S . Haifa isolates are shared with humans, raising concerns of microbial marine pollution.

Effect of ocean warming and acidification on the early life stages of subtropical Acropora spicifera - T. Foster; J. P. Gilmour; C. M. Chua; J. L. Falter; M. T. McCulloch (Coral Reefs, 2015)

Does tallgrass prairie restoration enhance the invasion resistance of post-agricultural lands? - Bryan L. Foster; Gregory R. Houseman; David R. Hall; Sarah E. Hinman (Biological Invasions, 2015)

Short-horned grasshopper subfamilies feed at different rates on big bluestem and switchgrass cultivars - Muhammad Irfan Ullah; Fatima Mustafa; William W. Hoback; Mathew L. Brust; Kerri M. Farnsworth-Hoback; John E. Foster (Biologia, 2015)

Erratum to: Widespread prevalence of cryptic Symbiodinium D in the key Caribbean reef builder, Orbicella annularis - Emma V. Kennedy; Nicola L. Foster; Peter J. Mumby; Jamie R. Stevens (Coral Reefs, 2015)

Widespread prevalence of cryptic Symbiodinium D in the key Caribbean reef builder, Orbicella annularis - Emma V. Kennedy; Nicola L. Foster; Peter J. Mumby; Jamie R. Stevens (Coral Reefs, 2015)

Climate remains an important driver of post‐European vegetation change in the eastern United States - Neil Pederson; Anthony W. D'Amato; James M. Dyer; David R. Foster; David Goldblum; Justin L. Hart; Amy E. Hessl; Louis R. Iverson; Stephen T. Jackson; Dario Martin‐Benito; Brian C. McCarthy; Ryan W. McEwan; et al. (Global Change Biology, 2015)

Erratum to: Variants within the MMP3 gene and patellar tendon properties in vivo in an asymptomatic population - Brandon Paul Foster; Christopher I. Morse; Gladys L. Onambele; Alun G. Williams (European Journal of Applied Physiology, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

mGluR5 positive allosteric modulation and its effects on MK-801 induced set-shifting impairments in a rat operant delayed matching/non-matching-to-sample task - Amber L. LaCrosse; Brian T. Burrows; Rachel M. Angulo; Phoebe R. Conrad; Sarah M. Himes; Nordia Mathews; Scott A. Wegner; Sara B. Taylor; M. Foster Olive (Psychopharmacology, 2015)

Evidence of land‐sea transfer of the zoonotic pathogen Campylobacter to a wildlife marine sentinel species - Johanna L. Baily; Guillaume Méric; Sion Bayliss; Geoffrey Foster; Simon E. Moss; Eleanor Watson; Ben Pascoe; Jane Mikhail; Romain Pizzi; Robert J. Goldstone; David G. E. Smith; Kim Willoughby; et al. (Molecular Ecology, 2015)
Environmental pollution often accompanies the expansion and urbanization of human populations where sewage and wastewaters commonly have an impact on the marine environments. Here, we explored the potential for faecal bacterial pathogens, of anthropic origin, to spread to marine wildlife in coastal areas. The common zoonotic bacterium Campylobacter was isolated from grey seals ( Halichoerus grypus ), an important sentinel species for environmental pollution, and compared to isolates from wild birds, agricultural sources and clinical samples to characterize possible transmission routes. Campylobacter jejuni was present in half of all grey seal pups sampled (24/50 dead and 46/90 live pups) in the breeding colony on the Isle of May (Scotland), where it was frequently associated with histological evidence of disease. Returning yearling animals (19/19) were negative for C . jejuni suggesting clearance of infection while away from the localized colony infection source. The genomes of 90 isolates from seals were sequenced and characterized using a whole‐genome multilocus sequence typing ( MLST ) approach and compared to 192 published genomes from multiple sources using population genetic approaches and a probabilistic genetic attribution model to infer the source of infection from MLST data. The strong genotype‐host association has enabled the application of source attribution models in epidemiological studies of human campylobacteriosis, and here assignment analyses consistently grouped seal isolates with those from human clinical samples. These findings are consistent with either a common infection source or direct transmission of human campylobacter to grey seals, raising concerns about the spread of human pathogens to wildlife marine sentinel species in coastal areas.

Variants within the MMP3 gene and patellar tendon properties in vivo in an asymptomatic population - Brandon Paul Foster; Christopher I. Morse; Gladys L. Onambele; Alun G. Williams (European Journal of Applied Physiology, 2014)

Seed and microsite limitations mediate stochastic recruitment in a low-diversity prairie restoration - Quinn Long; Bryan L. Foster; Kelly Kindscher (Plant Ecology, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Human COL5A1 rs12722 gene polymorphism and tendon properties in vivo in an asymptomatic population - Brandon Paul Foster; Christopher I. Morse; Gladys L. Onambele; Alun G. Williams (European Journal of Applied Physiology, 2014)

Spotted bat (Euderma maculatum) microsatellite discovery using illumina sequencing - Faith M. Walker; Jeffrey T. Foster; Kevin P. Drees; Carol L. Chambers (Conservation Genetics Resources, 2014)

Reply to letter: Acetaminophen and sport performance: doping or what? - Alexis R. Mauger; Lee Taylor; Bryna C. R. Chrismas; Samuel L. Watkins; Josh Foster (European Journal of Applied Physiology, 2014)

Propagule pressure-invasibility relationships: testing the influence of soil fertility and disturbance with Lespedeza cuneata - Gregory R. Houseman; Bryan L. Foster; Chad E. Brassil (Oecologia, 2014)

The influence of acetaminophen on repeated sprint cycling performance - Josh Foster; Lee Taylor; Bryna C. R. Chrismas; Samuel L. Watkins; Alexis R. Mauger (European Journal of Applied Physiology, 2014)

Metal accumulation in the greentail prawn, Metapenaeus bennettae, in Sydney and Port Hacking estuaries, Australia - K. L. M. Lewtas; G. F. Birch; C. Foster-Thorpe (Environmental Science and Pollution Research, 2014)

Metabolic potential of lithifying cyanobacteria-dominated thrombolitic mats - Jennifer M. Mobberley; Christina L. M. Khodadad; Jamie S. Foster (Photosynthesis Research, 2013)

Task Specialization and Odor Effects on Proboscis Extension Conditioning in Bumblebees (Bombus huntii) - Susannah Hannaford; Amelia Sattler; Jessica Siegel; Robin L. Foster (Journal of Insect Behavior, 2013)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Exercise-induced endocannabinoid signaling is modulated by intensity - David A. Raichlen; Adam D. Foster; Alexandre Seillier; Andrea Giuffrida; Gregory L. Gerdeman (European Journal of Applied Physiology, 2013)

Erratum to: A physiologically-based recirculatory meta-model for nasal fentanyl in man - Richard N. Upton; David J. R. Foster; Lona L. Christrup; Ola Dale; Kristin Moksnes; Lars Popper (Journal of Pharmacokinetics and Pharmacodynamics, 2013)

A physiologically-based recirculatory meta-model for nasal fentanyl in man - Richard N. Upton; David J. R. Foster; Lona L. Christrup; Ola Dale; Kristin Moksnes; Lars Popper (Journal of Pharmacokinetics and Pharmacodynamics, 2012)

Isolation and characterization of eight novel microsatellite loci in endangered Wyoming toad, Bufo baxteri - Renee M. Martin; Connie L. Keeler-Foster; Kenneth G. Boykin; Gerard Zegers; Wade D. Wilson (Conservation Genetics Resources, 2012)

Dramatic shifts in the gene pool of a managed population of an endangered species may be exacerbated by high genetic load - Andrew P. Martin; Anthony A. Echelle; Gerard Zegers; Sherri Baker; Connie L. Keeler-Foster (Conservation Genetics, 2012)

Effects of Bythotrephes longimanus (Crustacea, Cladocera) on the abundance, morphology, and prey community of Leptodora kindtii (Crustacea, Cladocera) - Sophie E. Foster; W. Gary Sprules; Angela L. Strecker (Hydrobiologia, 2012)

Submarine pyroclastic deposits formed during the 20th May 2006 dome collapse of the Soufrière Hills Volcano, Montserrat - J. Trofimovs; C. Foster; R. S. J. Sparks; S. Loughlin; A. Le Friant; C. Deplus; L. Porritt; T. Christopher; R. Luckett; P. J. Talling; M. R. Palmer; T. Le Bas (Bulletin of Volcanology, 2012)

Connectivity of Caribbean coral populations: complementary insights from empirical and modelled gene flow - NICOLA L. FOSTER; CLAIRE B. PARIS; JOHNATHAN T. KOOL; ILIANA B. BAUMS; JAMIE R. STEVENS; JUAN A. SANCHEZ; CAROLINA BASTIDAS; CLAUDIA AGUDELO; PHILLIPPE BUSH; OWEN DAY; RENATA FERRARI; PATRICIA GONZALEZ; et al. (Molecular Ecology, 2012)
Understanding patterns of connectivity among populations of marine organisms is essential for the development of realistic, spatially explicit models of population dynamics. Two approaches, empirical genetic patterns and oceanographic dispersal modelling, have been used to estimate levels of evolutionary connectivity among marine populations but rarely have their potentially complementary insights been combined. Here, a spatially realistic Lagrangian model of larval dispersal and a theoretical genetic model are integrated with the most extensive study of gene flow in a Caribbean marine organism. The 871 genets collected from 26 sites spread over the wider Caribbean subsampled 45.8% of the 1900 potential unique genets in the model. At a coarse scale, significant consensus between modelled estimates of genetic structure and empirical genetic data for populations of the reef‐building coral Montastraea annularis is observed. However, modelled and empirical data differ in their estimates of connectivity among northern Mesoamerican reefs indicating that processes other than dispersal may dominate here. Further, the geographic location and porosity of the previously described east–west barrier to gene flow in the Caribbean is refined. A multi‐prong approach, integrating genetic data and spatially realistic models of larval dispersal and genetic projection, provides complementary insights into the processes underpinning population connectivity in marine invertebrates on evolutionary timescales.

The potential significance of the breaching of small farm dams in the Sneeuberg region, South Africa - John Boardman; Ian D. L. Foster (Journal of Soils and Sediments, 2011)

Chrysoprase from Gumigil, Queensland - R. A. Eggleton; J. Fitz Gerald; L. Foster (Australian Journal of Earth Sciences, 2011)

Mechanisms of HIV-1 Nef Function and Intracellular Signaling - John L. Foster; Sarah J. Denial; Brenda R. S. Temple; J. Victor Garcia (Journal of Neuroimmune Pharmacology, 2011)

A blended global snow product using visible, passive microwave and scatterometer satellite data - James L. Foster; Dorothy K. Hall; John B. Eylander; George A. Riggs; Son V. Nghiem; Marco Tedesco; Edward Kim; Paul M. Montesano; Richard E. J. Kelly; Kimberly A. Casey; Bhaskar Choudhury (International Journal of Remote Sensing, 2011)

The synthetic triterpenoid CDDO-Imidazolide suppresses experimental liver metastasis - Jason L. Townson; Ian C. MacDonald; Karen T. Liby; Lisa Mackenzie; David W. Dales; Benjamin D. Hedley; Paula J. Foster; Michael B. Sporn; Ann F. Chambers (Clinical & Experimental Metastasis, 2011)

Darwin's special difficulty: the evolution of “neuter insects” and current theory - Francis L. W. Ratnieks; Kevin R. Foster; Tom Wenseleers (Behavioral Ecology and Sociobiology, 2011)

The potential for paleolimnology to determine historic sediment delivery to rivers - I. D. L. Foster; A. L. Collins; P. S. Naden; D. A. Sear; J. I. Jones; Y. Zhang (Journal of Paleolimnology, 2011)

Chitosan films are NOT antimicrobial - L. John R. Foster; Julian Butt (Biotechnology Letters, 2011)

Impacts of Oyster Reef Restoration on Primary Productivity and Nutrient Dynamics in Tidal Creeks of the North Central Gulf of Mexico - Rochelle Plutchak; Kelly Major; Just Cebrian; C. Drew Foster; Mary-Elizabeth C. Miller; Andrea Anton; Kate L. Sheehan; Kenneth L. Heck; Sean P. Powers (Estuaries and Coasts, 2010)

Hepatocellular hypertrophy and cell proliferation in Sprague–Dawley rats following dietary exposure to ammonium perfluorooctanoate occurs through increased activation of the xenosensor nuclear receptors PPARα and CAR/PXR - Clifford R. Elcombe; Barbara M. Elcombe; John R. Foster; David G. Farrar; Reinhard Jung; Shu-Ching Chang; Gerald L. Kennedy; John L. Butenhoff (Archives of Toxicology, 2010)

Damage to the reefs of Port Honduras Marine Reserve, Belize, during the 28 May 2009 earthquake - N. L. Foster; M. Williams; S. Chan; C. Ramirez; V. Vasquez (Coral Reefs, 2010)

Patch size effects on plant species decline in an experimentally fragmented landscape - Cathy D. Collins; Robert D. Holt; Bryan L. Foster (Ecology, 2009)
Understanding local and global extinction is a fundamental objective of both basic and applied ecology. Island biogeography theory (IBT) and succession theory provide frameworks for understanding extinction in changing landscapes. We explore the relative contribution of fragment size vs. succession on species' declines by examining distributions of abundances for 18 plant species declining over time in an experimentally fragmented landscape in northeast Kansas, USA. If patch size effects dominate, early‐successional species should persist longer on large patches, but if successional processes dominate, the reverse should hold, because in our system woody plant colonization is accelerated on large patches. To compare the patterns in abundance among patch sizes, we characterize joint shifts in local abundance and occupancy with a new metric: rank occupancy–abundance profiles (ROAPs). As succession progressed, statistically significant patch size effects emerged for 11 of 18 species. More early‐successional species persisted longer on large patches, despite the fact that woody encroachment (succession) progressed faster in these patches. Clonal perennial species persisted longer on large patches compared to small patches. All species that persisted longer on small patches were annuals that recruit from the seed bank each year. The degree to which species declined in occupancy vs. abundance varied dramatically among species: some species declined first in occupancy, others remained widespread or even expanded their distribution, even as they declined in local abundance. Consequently, species exhibited various types of rarity as succession progressed. Understanding the effect of fragmentation on extinction trajectories requires a species‐by‐species approach encompassing both occupancy and local abundance. We propose that ROAPs provide a useful tool for comparing the distribution of local abundances among landscape types, years, and species.

PanTHERIA: a species‐level database of life history, ecology, and geography of extant and recently extinct mammals - Kate E. Jones; Jon Bielby; Marcel Cardillo; Susanne A. Fritz; Justin O'Dell; C. David L. Orme; Kamran Safi; Wes Sechrest; Elizabeth H. Boakes; Chris Carbone; Christina Connolly; Michael J. Cutts; et al. (Ecology, 2009)
Analyses of life‐history, ecological, and geographic trait differences among species, their causes, correlates, and likely consequences are increasingly important for understanding and conserving biodiversity in the face of rapid global change. Assembling multispecies trait data from diverse literature sources into a single comprehensive data set requires detailed consideration of methods to reliably compile data for particular species, and to derive single estimates from multiple sources based on different techniques and definitions. Here we describe PanTHERIA, a species‐level data set compiled for analysis of life history, ecology, and geography of all known extant and recently extinct mammals. PanTHERIA is derived from a database capable of holding multiple geo‐referenced values for variables within a species containing 100 740 lines of biological data for extant and recently extinct mammalian species, collected over a period of three years by 20 individuals. PanTHERIA also includes spatial databases of mammalian geographic ranges and global climatic and anthropogenic variables. Here we detail how the data fields are extracted and defined for PanTHERIA using a customized data input format (MammalForm); how data were collected from the literature, species names and sources tracked, error‐checking and validation procedures applied, and how data were consolidated into species‐level values for each variable. Tables of the consolidated species‐level values are made available for each of two recent species‐level taxonomic classifications of mammals, as well as associated taxonomic synonymy conversion and data‐input files. This study provides a useful guide to prospective researchers on how to structure and codify life‐history, ecological, geographic, and taxonomic data and methods to extract meaningful species‐level traits. It also provides comprehensive information on traits like size, diet, environmental conditions, and ecology to permit macroecological and macroevolutionary analyses of this important clade. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

Community‐level consequences of mycorrhizae depend on phosphorus availability - Cathy D. Collins; Bryan L. Foster (Ecology, 2009)
In grasslands, arbuscular mycorrhizal fungi (AMF) mediate plant diversity; whether AMF increase or decrease diversity depends on the relative mycotrophy in dominant vs. subordinate plants. In this study we investigated whether soil nutrient levels also influence the ability of AMF to mediate plant species coexistence. First, we developed a conceptual model that predicts the influence of AMF on diversity along a soil nutrient gradient for plant communities dominated by mycotrophic and non‐mycotrophic species. To test these predictions, we manipulated phosphorus to create a soil nutrient gradient for mesocosm communities composed of native prairie grasses and then compared community properties for mesocosms with and without AMF. We found that, where P was limiting, AMF increased plant diversity and productivity, and also altered community structure; however, at high P, AMF had little influence on aboveground communities. Compositional differences among treatments were due largely to a trade‐off in the relative abundance of C 3 vs. C 4 species. Our study emphasizes how environmental constraints on mutualisms may govern community‐ and ecosystem‐level properties.

An integrated lake-catchment approach for determining sediment source changes at Aqualate Mere, Central England - Nathan J. Pittam; Ian D. L. Foster; Tim M. Mighall (Journal of Paleolimnology, 2009)

Geochronology and provenance of the Late Paleozoic accretionary wedge and Gympie Terrane, New England Orogen, eastern Australia∗ - R. J. Korsch; C. J. Adams; L. P. Black; D. A. Foster; G. L. Fraser; C. G. Murray; C. Foudoulis; W. L. Griffin (Australian Journal of Earth Sciences, 2009)

Lyophilization of Spodoptera frugiperda (Lepidoptera: Noctuidae) larvae yields high-quality DNA for use in AFLP genetic studies - Pete L. Clark; David J. Isenhour; Steven R. Skoda; Jaime Molina-Ochoa; Claudia Gianni; John E. Foster (International Journal of Tropical Insect Science, 2009)

Nature of the Weipa Bauxite deposit, northern Australia - G. Taylor; R. A. Eggleton; L. D. Foster; D. B. Tilley; M. Le Gleuher; C. M. Morgan (Australian Journal of Earth Sciences, 2008)

Regolith profile, mineralogy and geochemistry of the Weipa Bauxite, northern Australia - R. A. Eggleton; G. Taylor; M. Le Gleuher; L. D. Foster; D. B. Tilley; C. M. Morgan (Australian Journal of Earth Sciences, 2008)

Landscapes and regolith of Weipa, northern Australia - G. Taylor; R. A. Eggleton; L. D. Foster; C. M. Morgan (Australian Journal of Earth Sciences, 2008)

Population based models of cortical drug response: insights from anaesthesia - Brett L. Foster; Ingo Bojak; David T. J. Liley (Cognitive Neurodynamics, 2008)

Mineral magnetic signatures in a long core from Lake Qarun, Middle Egypt - I. D. L. Foster; F. Oldfield; R. J. Flower; K. Keatings (Journal of Paleolimnology, 2008)

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

The impact of Hurricane Ivan on the primary productivity and metabolism of marsh tidal creeks in the NorthCentral Gulf of Mexico - Just Cebrian; C. Drew Foster; Rochelle Plutchak; Kate L. Sheehan; Mary-Elizabeth C. Miller; Andrea Anton; Kelly Major; Kenneth L. Heck; Sean P. Powers (Aquatic Ecology, 2008)

Coexistence through spatio‐temporal heterogeneity and species sorting in grassland plant communities - Erin J. Questad; Bryan L. Foster (Ecology Letters, 2008)
The effect of spatial heterogeneity on species coexistence relies on the degree of niche heterogeneity in the habitat and the ability of species to exploit the available niche opportunities. We studied species coexistence in a perennial grassland, and tested whether small‐scale disturbances create environmental heterogeneity that affects coexistence and whether the functional diversity of species in the species pool affects the ability of community composition to reflect heterogeneity through species sorting. We manipulated the spatio‐temporal heterogeneity of disturbance and the functional diversity of species added as seed and measured their impact on the spatial turnover of species composition. Disturbance increased environmental heterogeneity and spatial turnover, and the effect of heterogeneity on turnover was greatest in the presence of a functionally diverse species pool, showing the importance of trait variation among species for exploiting environmental heterogeneity, and suggesting that coexistence occurred due to species sorting among heterogeneous niches.

In vivo deuteration strategies for neutron scattering analysis of bacterial polyhydroxyoctanoate - Robert A. Russell; Peter J. Holden; Karyn L. Wilde; Christopher J. Garvey; Kerie M. Hammerton; L. John R. Foster (European Biophysics Journal, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

The USP Performance Verification Test, Part II: Collaborative Study of USP’s Lot P Prednisone Tablets - Maria Glasgow; Shawn Dressman; William Brown; Thomas Foster; Stefan Schuber; Ronald G. Manning; Samir Z. Wahab; Roger L. Williams; Walter W. Hauck (Pharmaceutical Research, 2008)

Evidence of local evolution of tomato-infecting begomovirus species in West Africa: characterization of tomato leaf curl Mali virus and tomato yellow leaf crumple virus from Mali - Y.-C. Zhou; M. Noussourou; T. Kon; M. R. Rojas; H. Jiang; L.-F. Chen; K. Gamby; R. Foster; R. L. Gilbertson (Archives of Virology, 2008)

Synthesis and pharmacological evaluation of m-terphenyl amines as cyclooxygenase inhibitors - John D. Bauer; Michael S. Foster; Jeffrey D. Hugdahl; Kristi L. Burns; Sheldon W. May; Stanley H. Pollock; Horace G. Cutler; Stephen J. Cutler (Medicinal Chemistry Research, 2007)

Population pharmacokinetics of buprenorphine following a two-stage intravenous infusion in healthy volunteers - Mette L. Jensen; David J. R. Foster; Richard N. Upton; Kim Kristensen; Steen H. Hansen; Niels-Henrik Jensen; Bettina N. Nielsen; Ulrik Skram; Hanne H. Villesen; Lona Christrup (European Journal of Clinical Pharmacology, 2007)

Genetic structure and evolved malaria resistance in Hawaiian honeycreepers - JEFFREY T. FOSTER; BETHANY L. WOODWORTH; LORI E. EGGERT; PATRICK J. HART; DANIELLE PALMER; DAVID C. DUFFY; ROBERT C. FLEISCHER (Molecular Ecology, 2007)
Infectious diseases now threaten wildlife populations worldwide but population recovery following local extinction has rarely been observed. In such a case, do resistant individuals recolonize from a central remnant population, or do they spread from small, perhaps overlooked, populations of resistant individuals? Introduced avian malaria ( Plasmodium relictum ) has devastated low‐elevation populations of native birds in Hawaii, but at least one species (Hawaii amakihi, Hemignathus virens ) that was greatly reduced at elevations below about 1000 m tolerates malaria and has initiated a remarkable and rapid recovery. We assessed mitochondrial and nuclear DNA markers from amakihi and two other Hawaiian honeycreepers, apapane ( Himatione sanguinea ) and iiwi ( Vestiaria coccinea ), at nine primary study sites from 2001 to 2003 to determine the source of re‐establishing birds. In addition, we obtained sequences from tissue from amakihi museum study skins (1898 and 1948–49) to assess temporal changes in allele distributions. We found that amakihi in lowland areas are, and have historically been, differentiated from birds at high elevations and had unique alleles retained through time; that is, their genetic signature was not a subset of the genetic variation at higher elevations. We suggest that high disease pressure rapidly selected for resistance to malaria at low elevation, leaving small pockets of resistant birds, and this resistance spread outward from the scattered remnant populations. Low‐elevation amakihi are currently isolated from higher elevations (> 1000 m) where disease emergence and transmission rates appear to vary seasonally and annually. In contrast to results from amakihi, no genetic differentiation between elevations was found in apapane and iiwi, indicating that slight variation in genetic or life‐history attributes can determine disease resistance and population recovery. Determining the conditions that allow for the development of resistance to disease is essential to understanding how species evolve resistance across a landscape of varying disease pressures.

Cotreatment with the kappa opioid agonist U69593 enhances locomotor sensitization to the D2/D3 dopamine agonist quinpirole and alters dopamine D2 receptor and prodynorphin mRNA expression in rats - Melissa L. Perreault; Dawn Graham; Sarah Scattolon; Yufang Wang; Henry Szechtman; Jane A. Foster (Psychopharmacology, 2007)

Vole disturbances and plant diversity in a grassland metacommunity - Erin J. Questad; Bryan L. Foster (Oecologia, 2007)

Experimental analysis of worker division of labor in bumblebee nest thermoregulation (Bombus huntii, Hymenoptera: Apidae) - Kathryn E. Gardner; Robin L. Foster; Sean O’Donnell (Behavioral Ecology and Sociobiology, 2007)

Pycnoporus cinnabarinus is pathogenic on living Paulownia trees - K. L. Bayliss; C. Foster; B. Dell; G. E. St. J. Hardy (Australasian Plant Pathology, 2007)

Incorporation of Plant Residues into Soil Organic Matter Fractions With Grassland Management Practices in the North American Midwest - S. A. Billings; C. M. Brewer; B. L. Foster (Ecosystems, 2006)

Re-engineering the target specificity of clostridial neurotoxins - a route to novel therapeutics - Keith A. Foster; Emily J. Adams; Lyndsey Durose; Caroline J. Cruttwell; Elizabeth Marks; Clifford C. Shone; John A. Chaddock; Clare L. Cox; Charlotte Heaton; J. Mark Sutton; Jonathan Wayne; Frances C. G. Alexander; et al. (Neurotoxicity Research, 2006)

Anxiogenic and aversive effects of corticotropin-releasing factor (CRF) in the bed nucleus of the stria terminalis in the rat: role of CRF receptor subtypes - Lacey L. Sahuque; Erika F. Kullberg; Andrew J. Mcgeehan; Jennifer R. Kinder; Megan P. Hicks; Mary G. Blanton; Patricia H. Janak; M. Foster Olive (Psychopharmacology, 2006)

Post-depositional 137Cs Mobility in the Sediments of Three Shallow Coastal Lagoons, SW England - I. D. L. Foster; T. M. Mighall; H. Proffitt; D. E. Walling; P. N. Owens (Journal of Paleolimnology, 2006)

The Definition of British Water Beetle Species Pools (Coleoptera) and their Relationship to Altitude, Temperature, Precipitation and Land Cover Variables - M. D. Eyre; G. N. Foster; M. L. Luff; S. P. Rushton (Hydrobiologia, 2006)

Modelling the spread of scrapie in a sheep flock: evidence for increased transmission during lambing seasons - S. Touzeau; M. E. Chase-Topping; L. Matthews; D. Lajous; F. Eychenne; N. Hunter; J. D. Foster; G. Simm; J.-M. Elsen; M. E. J. Woolhouse (Archives of Virology, 2006)

Relative contributions of adjacent species set and environmental conditions to plant community richness and composition in a group of created wetlands - Sharon M. Ashworth; Bryan L. Foster; Kelly Kindscher (Wetlands, 2006)

Character and distribution of exposed glaciodeltaic deposits off outer Cape Cod, Massachusetts, and their effects on hydrogeology and benthic habitats - L. J. Poppe; D. S. Foster; W. W. Danforth (Geo-Marine Letters, 2006)

Chemical Partitioning to Foliage: The Contribution and Legacy of Davide Calamari - Donald Mackay; Karen L. Foster; Zaheerabbas Patwa; Eva Webster (Environmental Science and Pollution Research, 2006)

Patch dynamics of coral reef macroalgae under chronic and acute disturbance - Peter J. Mumby; Nicola L. Foster; Elizabeth A. Glynn Fahy (Coral Reefs, 2005)

Carbon monoxide levels at a toll plaza near Durban, South Africa - R. D. Diab; S. J. Foster; K. François; B. S. Martincigh; L. F. Salter (Environmental Chemistry Letters, 2005)

Acute Toxicity Value Extrapolation with Fish and Aquatic Invertebrates - Denny R. Buckler; Foster L. Mayer; Mark R. Ellersieck; Amha Asfaw (Archives of Environmental Contamination and Toxicology, 2005)

Identification Of Sex Pheromone Components Of The Painted Apple Moth: A Tussock Moth With A Thermally Labile Pheromone Component - A. M. El-Sayed; A. R. Gibb; D. M. Suckling; B. Bunn; S. Fielder; D. Comeskey; L. A. Manning; S. P. Foster; B. D. Morris; T. ando; K. Mori (Journal of Chemical Ecology, 2005)

Oral Dosage Form Performance Tests: New Dissolution Approaches - Walter W. Hauck; Thomas Foster; Eric Sheinin; Todd Cecil; William Brown; Margareth Marques; Roger L. Williams (Pharmaceutical Research, 2005)

Comparing the effects of farming practices on ground beetle (Coleoptera: Carabidae) and spider (Araneae) assemblages of Scottish farmland - Lorna J. Cole; David I. McCracken; Iain S. Downie; Peter Dennis; Garth N. Foster; Tony Waterhouse; Kevin J. Murphy; Anna L. Griffin; Mike P. Kennedy (Biodiversity and Conservation, 2005)

Investigations on the causes of upper stem rot (USR) on standing mature oil palms - Y. Hasan; H. L. Foster; J. Flood (Mycopathologia, 2005)

Exploring the relationship between land cover and the distribution of water beetle species (Coleoptera) at the regional scale - M. D. Eyre; G. N. Foster; M. L. Luff (Hydrobiologia, 2005)

U-Pb columbite-tantalite chronology of rare-element pegmatites using TIMS and Laser Ablation-Multi Collector-ICP-MS - S. R. Smith; G. L. Foster; R. L. Romer; A. G. Tindle; S. P. Kelley; S. R. Noble; M. Horstwood; F. W. Breaks (Contributions to Mineralogy and Petrology, 2004)

Long‐Term Population Changes of Native and Introduced Birds in the Alaka‘i Swamp, Kaua‘i - JEFFREY T. FOSTER; ERIK J. TWEED; RICHARD J. CAMP; BETHANY L. WOODWORTH; COREY D. ADLER; TOM TELFER (Conservation Biology, 2004)
Within the last 30 years, five endemic bird species of the Alaka‘i Swamp, Kaua‘i, Hawai‘i, have likely gone extinct. We documented population trends of the remaining avifauna in this time period to identify a common pattern in the Hawaiian Islands: decline of native species and expansion of introduced species. We conducted bird surveys over 100 km 2 of the Alaka‘i and Kōke‘e regions of Kaua‘i in March–April 2000 to estimate population size, distribution, and range limits of seven native and six introduced forest birds. We compared the results with four previous surveys conducted over the last 30 years. Five of the seven native species we studied have fared well, maintaining sizeable populations (>20,000 individuals) and unchanged or increasing numbers. The endemic ‘Akikiki ( Oreomystis bairdi ), however, declined from 6296 (SE ± 1374) to 1472 (SE ± 680) individuals and exhibited range contraction from 88 to 36 km 2 . The ‘I‘iwi ( Vestiaria coccinea ) also experienced a decline and contraction, though not as severe. Populations of several introduced forest birds are increasing, but all species, excluding the Japanese White‐eye ( Zosterops japonicus ), were at low numbers ( Cettia diphone ) recently invaded, whereas another, the Red‐billed Leiothrix ( Leiothrix lutea ), has been extirpated. Two hurricanes in the past 20 years appear to have most strongly affected nectarivores and may have contributed to the decline or extinction of several other species. Overall, native bird populations on Kaua‘i have exhibited species‐specific responses to limiting factors. Although most native populations appear stable, the extant native avifauna is vulnerable as a result of limited distributions and the potential for widespread habitat degradation.

A high affinity ligand for GABA A -receptor containing a 5 subunit antagonizes ethanol?s neurobehavioral effects in Long-Evans rats - Peter F. McKay; Katrina L. Foster; Dynesha Mason; Shannan McCane; Xiaohui He; Harry L. June; James M. Cook; Rancia Cummings; Marin Garcia; La Shone Williams; Collette Grey (Psychopharmacology, 2004)

Localization and expression of the glutamate transporter, excitatory amino acid transporter 4, within astrocytes of the rat retina - Michelle M. Ward; Theresa Puthussery; Lisa E. Foster; Erica L. Fletcher; Andrew I. Jobling (Cell and Tissue Research, 2004)

Complete nucleotide sequence and analysis of pPSR1 (72,601 bp), a pPT23A-family plasmid from Pseudomonas syringae pv. syringae A2 - G. W. Sundin; C. T. Mayfield; Y. Zhao; T. S. Gunasekera; G. L. Foster; M. S. Ullrich (Molecular Genetics and Genomics, 2004)

An investigation into the relationship between water beetle (Coleoptera) distribution and land cover in Scotland and northeast England - M. D. Eyre; G. N. Foster; M. L. Luff; J. R. Staley (Journal of Biogeography, 2003)
Aims To determine the relationship between satellite‐derived land cover data and distribution patterns of water beetle species pools. Location A total of 687 British national grid 10 km squares in Scotland and 588 1 km grid squares in 99 10 km grid squares in northeast England. Methods Multivariate classification and constrained ordination analyses were used with water beetle species and land cover data. Results The major variation in both the Scotland and northeast England 10 km species pools was from squares with upland acid water habitats to squares with lowland fens and ponds whilst for the 1 km northeast England data it was from squares dominated by fast‐flowing streams and rivers to those with fens and ponds. The secondary variations in the 10 and 1 km analyses were the primary ones juxtaposed. Constrained ordination of the Scottish 10 km data showed upland land cover types to be most influential in determining species pool distribution whilst lowland covers were more important with both the 10 and 1 km northeast England pools. The three analyses showed that coastal cover had a relatively high influence on species pool distribution but no species pool group was dominated by coastal species. Main conclusions There were strong relationships between water beetle species pool distributions and the satellite‐derived land cover types dominating upland and lowland areas. The major variation in the northeast England species pool data differed at the two scales analysed. Results indicated that there is considerable potential for the synthesis of water beetle distribution and land cover data for use in environmental and conservation monitoring at both the regional and national scales.

Tachykinin substance P signaling involved in diesel exhaust-induced bronchopulmonary neurogenic inflammation in rats - Simon S. Wong; Nina N. Sun; Ingegerd Keith; Chol-Bum Kweon; David E. Foster; James J. Schauer; Mark L. Witten (Archives of Toxicology, 2003)

Changing suspended sediment and particulate phosphorus loads and pathways in underdrained lowland agricultural catchments; Herefordshire and Worcestershire, U.K. - I. D. L. Foster; A. S. Chapman; R. M. Hodgkinson; A. R. Jones; J. A. Lees; S. E. Turner; M. Scott (Hydrobiologia, 2003)

Comparison of Human Duodenum and Caco-2 Gene Expression Profiles for 12,000 Gene Sequences Tags and Correlation with Permeability of 26 Drugs - Duxin Sun; Hans Lennernas; Lynda S. Welage; Jeffery L. Barnett; Christopher P. Landowski; David Foster; David Fleisher; Kyung-Dall Lee; Gordon L. Amidon (Pharmaceutical Research, 2002)

Landscape patterns of hemlock decline in New England due to the introduced hemlock woolly adelgid - David A. Orwig; David R. Foster; David L. Mausel (Journal of Biogeography, 2002)
Aim The hemlock woolly adelgid (HWA; Adelges tsugae Annand), a small, aphid‐like insect native to Japan, is currently migrating northward through eastern North America and threatens to eliminate eastern hemlock [ Tsuga canadensis (L.) Carriere], one of the most abundant, long‐lived shade tolerant species, across its range. The major objectives of this study were: (1) to characterize the pre‐HWA distribution, composition, and structure of hemlock stands; (2) to characterize the spatial patterns of damage generated by HWA across southern New England since the time of its arrival in 1985; and (3) to examine environmental and stand factors that are associated with declines in crown vigour and mortality of hemlock. Location Our study was conducted in a 4900‐km 2 study region extending from Long Island Sound northward to the Massachusetts border and including the Connecticut River Valley in Connecticut, USA. Methods Aerial photographs and extensive field study were used to map and develop GIS overlays of 1000 hemlock stands in our study region. Intensive sampling of a random selection of 114 hemlock stands across the study area was used to document patterns of hemlock infestation, vigour, and mortality in relation to stand and site characteristics. Mantel tests were utilized to assess the relative importance of environmental and stand variables in controlling the intensity of HWA infestation and damage. Results Most stands were located along ridge tops, steep hillsides and narrow valleys. Hemlock importance values ranged from 22 to 96% and stand densities varied from 300 to 1450 stems ha – 1 . Adelgid presence and adelgid‐induced hemlock mortality were found in 88 and 74% of the sampled forests, respectively. Approximately 25% of stands were logged recently, ranging in intensity from partial hemlock cutting to large clearcuts. A geographical trend in reduced HWA infestation intensity and tree mortality and enhanced crown vigour of overstory and understory hemlock occurs from south to north, coincident with the temporal colonization pattern of HWA. Mantel analyses indicated that patterns of HWA infestation, hemlock mortality, and crown vigour were most strongly correlated with latitude. Mortality was also weakly related to aspect and stand size. Average mortality was highest on western aspects but exceeded 20% on most slopes. Remaining trees averaged over 50% foliar loss, with no significant difference among aspects. Main conclusions Results suggest that as HWA becomes abundant, stands on xeric aspects succumb rapidly, but that stand and landscape variables such as overstory composition and structure, slope, and elevation, exert little control over susceptibility or eventual mortality. Ultimately, duration of infestation controls the intensity of hemlock decline and mortality. Over 4290 ha of hemlock forest have been eliminated by logging or HWA just within the southern part of our transect since the mid‐1980s, and we predict continued HWA infestation will lead to unprecedented hemlock loss throughout the north‐eastern USA, regardless of site conditions or location.

Direct and indirect ecosystem consequences of an invasive pest on forests dominated by eastern hemlock - Matthew L. Kizlinski; David A. Orwig; Richard C. Cobb; David R. Foster (Journal of Biogeography, 2002)
Aim This study compares the magnitude and trajectory of vegetation and ecosystem function dynamics associated with the direct impact of hemlock woolly adelgid ( Adelges tsugae Annand; HWA) infestation vs. the indirect consequences of HWA‐induced damage in the form of salvage and pre‐emptive logging of hemlock [ Tsuga canadensis (L.) Carriere] forests. Location The study was conducted within an area extending from southern Connecticut up to and including the Connecticut River lowlands west to the Berkshire Plateau in central Massaschusetts, USA. Methods Overstorey and understorey vegetation and ecosystem function parameters such as decomposition and nitrogen cycling were examined in logged and unlogged portions of ten hemlock stands varying in HWA damage intensity. Results Intensive hemlock logging generated more rapid and pronounced microenvironment and vegetation changes than chronic HWA damage. Black birch ( Betula lenta L.) seedling densities and percent cover of brambles ( Rubus L. spp.), sedges ( Carex L. spp.) and hay‐scented fern ( Dennstaedtia punctilobula Michx.) were significantly higher in recent harvests vs. HWA‐damaged and undamaged sites. High black birch sapling densities (>7000 ha −1 ) were common in the older harvests but not in adjacent, HWA‐damaged portions of these sites. Undamaged sites had 20% more forest floor mass than HWA‐damaged sites and double the mass of older cuts. Mass loss rates of cellulose paper suggest that conditions were more favourable for decomposition in the damaged and older logged sites. Recently cut sites had significantly larger inorganic N pools than undamaged forests, although total net nitrogen (N) mineralization rates were not significantly different among treatments. Nitrification rates of 0.2 kg ha −1 day −1 measured in the oldest cuts were three times greater than in HWA‐damaged sites and over 200 times greater than in undamaged hemlock sites. However, resin bag capture in the older cuts was similar to amounts captured in undamaged and damaged forests, suggesting that excess nitrogen was being utilized in vegetative uptake. In contrast, relatively large amounts of ammonium and nitrate captured in recent harvests indicate higher N availability, less vegetative uptake, and a greater potential for N leaching. Main conclusions Results suggest that both the decline associated with HWA infestation and the indirect effects of HWA in the form of logging are generating profound changes in structure, composition, and ecosystem function in these forests, although at different spatial and temporal scales. Hemlock harvesting imposed more abrupt microenvironmental changes, and rapidly reduced vegetative cover while chronic HWA infestation led to gradually thinning canopies. Both disturbances led to black birch dominated forests, although logging resulted in greater amounts of shade‐intolerant regeneration, higher soil pH and nitrification rates, and reduced forest floor mass. Pre‐emptive cutting of undamaged forests may lead to greater N losses than those associated with HWA infestation or logging of deteriorated hemlock forests, because of reduced vegetative uptake. Silvicultural methods that allow for vegetation establishment prior to harvesting will probably lessen the ecological impacts of hemlock removal.

A constitutive gene expression system derived from the tCUP cryptic promoter elements - K. Malik; K. Wu; X.-Q. Li; T. Martin-Heller; M. Hu; E. Foster; L. Tian; C. Wang; K. Ward; M. Jordan; D. Brown; S. Gleddie; et al. (Theoretical and Applied Genetics, 2002)

Island theory, matrix effects and species richness patterns in habitat fragments - William M. Cook; Kurt T Lane; Bryan L. Foster; Robert D. Holt (Ecology Letters, 2002)
Island biogeography theory, created initially to study diversity patterns on islands, is often applied to habitat fragments. A key but largely untested assumption of this application of theory is that landscape matrix species composition is non‐overlapping with that of the islands. We tested this assumption in successional old field patches in a closely mowed matrix, and because our patches are appropriately viewed as sets of contiguous habitat units we studied patterns of species richness per unit area. Previous studies at our site did not find that diversity patterns on patch ‘islands’ conformed to predictions of island biogeography theory. Our results indicate that when matrix species are removed from the patch samples, diversity patterns conform better to theory. We suggest that classical island theory remains an appropriate tool to study diversity patterns in fragmented habitats, but that allowances should be made for spill‐over colonization of ‘islands’ from the ‘sea’.

Worker policing in the European hornet Vespa crabro - K. R. Foster; J. Gulliver; F. L. W. Ratnieks (Insectes Sociaux, 2002)

Constraints on colonization and species richness along a grassland productivity gradient: the role of propagule availability - Bryan L. Foster (Ecology Letters, 2001)
An important goal in ecology is to discern under what habitat conditions community structure is primarily regulated by local ecological interactions and under what conditions community structure is more regulated by the pool of available colonists. I conducted a seed addition experiment in successional grassland to evaluate the relative significance of neighbourhood biotic interactions and propagule availability in regulating plant colonization and species richness along a natural gradient of grassland productivity. In undisturbed field plots, seed additions of 34 species led to an increase in species richness in locations of low productivity, an effect that declined in magnitude as productivity increased. In disturbed plots, seed additions led to a relatively constant increase in species richness at all levels of productivity. The results support the hypothesis that the role of propagule availability in regulating colonization dynamics and species richness declines in significance relative to local‐scale competitive interactions as habitat productivity increases.

Enhancers and core promoter elements are essential for the activity of a cryptic gene activation sequence from tobacco, tCUP - K. Wu; K. Malik; L. Tian; M. Hu; T. Martin; E. Foster; D. Brown; B. Miki (Molecular Genetics and Genomics, 2001)

Statistical Analysis of Spatial Pattern: A Comparison of Grid and Hierarchical Sampling Approaches - R. G. Cole; T. R. Healy; M. L. Wood; D. M. Foster (Environmental Monitoring and Assessment, 2001)

Population dynamics of a scrapie outbreak - L. Matthews; P. G. Coen; J. D. Foster; N. Hunter; M. E. J. Woolhouse (Archives of Virology, 2001)

Colony kin structure and male production in Dolichovespula wasps - Kevin R. Foster; Francis L. W. Ratnieks; Niclas Gyllenstrand; Peter A. Thorén (Molecular Ecology, 2001)
In annual hymenopteran societies headed by a single outbred queen, paternity (determined by queen mating frequency and sperm use) is the sole variable affecting colony kin structure and is therefore a key predictor of colony reproductive characteristics. Here we investigate paternity and male production in five species of Dolichovespula wasps. Twenty workers from each of 10 colonies of each of five species, 1000 workers in total, were analysed at three DNA microsatellite loci to estimate paternity. To examine the relationship between kin structure and reproductive behaviour, worker ovary activation was assessed by dissection and the maternal origin of adult males was assessed by DNA microsatellites. Effective paternity was low in all species ( D. media 1.08, D. maculata 1.0, D. sylvestris 1.15, D. norwegica 1.08 and D. saxonica 1.35), leading to the prediction of queen–worker conflict over male production. In support of this, workers with full‐size eggs in their ovaries (four out of five species) and adult males that were workers’ sons (all five species) were found in queenright colonies. However, workers were only responsible for a minority of male production ( D. media 7.4%, D. maculata 20.9%, D. sylvestris 9.8%, D. norwegica 2.6% and D. saxonica 34.6%) suggesting that the queen maintains considerable reproductive power over the workers. Kin structure and reproductive conflict in Dolichovespula contrast with their sister group Vespula . Dolichovespula is characterized by low paternity, worker reproduction, and queen–worker conflict and Vespula by high paternity, effective worker policing and absence of worker reproduction. The trend revealed by this comparison is as predicted by kin selection theory suggesting that colony kin structure has been pivotal in the evolution of the yellowjacket wasps.

Extinction and spontaneous recovery of ataxic tolerance to ethanol in rats - Douglas C. Brooks; Boghos R. Karamanlian; Vicki L. Foster (Psychopharmacology, 2001)

Competition at the population level along a standing crop gradient: a field experiment in successional grassland - Bryan L. Foster (Plant Ecology, 2000)

Do hornets have zombie workers? - Kevin R. Foster; Francis L. W. Ratnieks; Alan F. Raybould (Molecular Ecology, 2000)
Colonies of the European hornet, Vespa crabro , are typically founded by a single queen mated to a single male . From the resulting colony relatedness pattern we predicted strong worker–queen conflict over male production where both the workers and the queen attempt to produce the colony’s males. To test for this conflict, male production was studied in 15 hornet nests using a combination of DNA microsatellite analysis (282 males), worker ovary dissections (500 workers from eight nests) and 50 h of observation (four nests). In contrast to our prediction, the data show that hornet males are queens’ sons, that workers never attempt to lay eggs, rarely have activated ovaries, and that there is no direct aggression between the queen and the workers. This contrasts with other data for vespine wasps, which support relatedness predictions. Dolichovespula arenaria has the same kin structure as V. crabro and workers produce males in many colonies. The similarity between these two species makes it difficult to explain why workers do not reproduce in V. crabro . Self‐restraint is expected if worker reproduction significantly reduces colony productivity but there is no obvious reason why this should be important to V. crabro but not to D. arenaria . Alternatively, queen control may be important. The absence of expressed queen–worker conflict rules out physical control. Indirect pheromonal control is a possibility and is supported by the occurrence of royal courts and queen pheromone in Vespa but not Dolichovespula . Pheromonal queen control is considered evolutionarily unstable, but could result from a queen–worker arms race over reproductive control in which the queen is ahead. The genetic data also revealed diploid males in one colony, the first example in the vespine wasps, and two colonies with double matrilines, suggesting that occasional usurpation by spring queens occurs.

Dynamic and static views of succession: Testing the descriptive power of the chronosequence approach - Bryan L. Foster; David Tilman (Plant Ecology, 2000)

Seasonal Changes and Tissue Distribution of Mercury in Largemouth Bass ( Micropterus salmoides ) from Dorena Reservoir, Oregon - E. P. Foster; D. L. Drake; G. DiDomenico (Archives of Environmental Contamination and Toxicology, 2000)

Low paternity in the hornet Vespa crabro indicates that multiple mating by queens is derived in vespine wasps - Kevin R. Foster; Perttu Seppä; Francis L. W. Ratnieks; Peter A. Thorén (Behavioral Ecology and Sociobiology, 1999)

A tobacco cryptic constitutive promoter, tCUP, revealed by T-DNA tagging - Elizabeth Foster; Jiro Hattori; Hélène Labbé; Thérèse Ouellet; Pierre R. Fobert; Lisa E. James; V.N. Iyer; Brian L. Miki (Plant Molecular Biology, 1999)

Analysis of a translational enhancer present within the 5′-terminal sequence of the genomic RNA of potato virus S - R. L. Turner; M. Glynn; S. C. Taylor; M.-K. Cheung; C. Spurr; D. Twell; G. D. Foster (Archives of Virology, 1999)

Tissue-Specific Fatty Acid Composition of Glandular Trichomes of Mite-Resistant and -Susceptible Pelargonium xhortorum - R. A. Grazzini; P. R. Paul; T. Hage; D. L. Cox-Foster; J. I. Medford; R. Craig; R. O. Mumma (Journal of Chemical Ecology, 1999)

The communicative meaning of body oscillations in the social wasp, Polistes fuscatus (Hymenoptera, Vespidae) - J. L. Savoyard; G. J. Gamboa; D. L. D. Cummings; R. L. Foster (Insectes Sociaux, 1998)

Impact of Human Activity on Regional Forest Composition and Dynamics in Central New England - Janice L. Fuller; David R. Foster; Jason S. McLachlan; Natalie Drake (Ecosystems, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

The biodegradation of poly-3-hydroxyalkanoates, PHAs, with long alkyl substitutents byPseudomonas maculicola - L. J. R. Foster; S. J. Zervas; R. W. Lenz; R. C. Fuller (Biodegradation, 1995)

Comparison of rectangular and exponential current pulses for evoking sensation - Jerry L. Wessale; Leslie A. Geddes; Gregory M. Ayers; Kirk S. Foster (Annals of Biomedical Engineering, 1992)

Effects of stage of colony cycle, context, and intercolony distance on conspecific tolerance by paper wasps (Polistes fuscatus) - George J. Gamboa; Robin L. Foster; Julie A. Scope; Angela M. Bitterman (Behavioral Ecology and Sociobiology, 1991)

Myxoviruses do not induce non-specific alterations in membrane permeability early on in infection - K. A. Foster; K. J. Micklem; G. Agnarsdottir; C. L. Lancashire; N. N. Bogomolova; Y. S. Boriskin; C. A. Pasternak (Archives of Virology, 1983)

Residue dynamics and biological effects of polychlorinated biphenyls in aquatic organisms - Foster L. Mayer; Paul M. Mehrle; Herman O. Sanders (Archives of Environmental Contamination and Toxicology, 1977)

Genetics of lucilin, a storage protein from the sheep blowfly, Lucilia cuprina (Calliphoridae) - John A. Thomson; Karen R. Radok; Denis C. Shaw; Maxwell J. Whitten; Geoffrey G. Foster; L. Michael Birt (Biochemical Genetics, 1976)

Ionic and non-ionic compounds in the germination of spores of bacillus megaterium texas - L. J. Rode; J. W. Foster (Archives of Microbiology, 1962)

Ionic germination of spores of bacillus megaterium QM B1551 - L. J. Rode; J. W. Foster (Archives of Microbiology, 1962)

The action of surfactants on bacterial spores - L. J. Rode; J. W. Foster (Archives of Microbiology, 1960)

Sectional notes - C. L. Fitch; E. L. Newdick; Frank W. Hussey; Ralph W. Donaldson; J. R. Livermore; E. B. Lyman; Robert Schmidt; E. J. Taintor; E. B. Tussing; J. B. R. Dickey; K. W. Lauer; G. S. Ralston; et al. (American Journal of Potato Research, 1934)